Long-term lithium exposure induces persistent physiological and methylation-associated alterations in Chromochloris zofingiensis: An integrated multi-omics analysis - Rui Feng; Ziyue Zhang; Xiaoxi Shui; Jiayin Wang; Congying Wang; Pengda Yan; Zhao Zhang; Baohua Zhao; Dongzhe Sun (Environmental Pollution, 2026)

Competitive hydrated eutectic electrolyte for 9650 h long-lived aqueous Zn-ion batteries with wide-temperature operability - Haowen Xiang; Yan Qin; Kaiwen Zhang; Yao Zhang; Jinda Wang; Rui Zhao; Fushao Li; Xinyue Liang; Xuefeng Zou (Chemical Engineering Journal, 2026)

Interfacial electronic coupling in Bi2O3/COF heterostructures for high-performance supercapacitors - Rui Zhang; Hong-xia Gao; Yu-ting Zhao; Li Li; Yan Lv; Xue-yan Wu; Jixi Guo; Rui Xue (Chemical Engineering Journal, 2026)

Soliton solutions, spectral classification and asymptotic analysis for the shifted nonlocal modified nonlinear Schrödinger equation with nonzero background - Xin-Yu Liu; Yan-Nan Zhao; Rui Guo (Wave Motion, 2026)

Description of two novel Marinobacter species isolated from saline-alkali soil: Marinobacter alkalisoli sp. nov. and Marinobacter shunpengi sp. nov - Jing-Yan Zhao; Lian Xu; Rui-Qi Sun; Mei-Qian Song; Jia-Hui Zeng; Hua-Mei Wei; Ji-Quan Sun (Systematic and Applied Microbiology, 2026)

Early Cretaceous Jehol Biota in the Qinling Orogenic Belt: palaeobiogeographical and palaeoecological implications - Siyu Song; Xin Zhang; Xiao Teng; Ting Li; Tingting Yu; Jiahao Li; Yan Xue; Peihan Liu; Rui Fang; Xiangdong Zhao; Daran Zheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Evaluation and forecasting of habitat suitability and thermal growth responses in the mud clam Geloina coaxans under climate change - Bing-Xian Liu; Yu-Yang Zhang; Cheng-Rui Yan; Zhan-Wei Zhao; Ning Zhang; Lin-Xuan Ma; Xian-Bo Qiu; Yun-Wei Dong (Marine Environmental Research, 2026)

Corrigendum to “TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy” [J Hazard Mater 494 (2025) 138515] - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2026)

Dietary ellagic acid improves glucose and lipid homeostasis with concurrent gut microbiota and serum metabolome remodeling in db/db mice - Rui-Bo Jia; Weipei Li; Pengru Yan; Chunxia Zhou; Zirui Huang; Mouming Zhao (Food Bioscience, 2026)

CXCL8 is associated with aflatoxin B1–triggered injury and caspase-3 activation in porcine kidney epithelial PK15 cells: integrated transcriptomics and CRISPR/Cas9 knockout - Jianlin Yuan; Yuhan Ma; Jinfeng Li; Xizhu Chen; Yiping Wen; Rui Wu; Xinfeng Hang; Heng Huang; Senyan Du; Yiping Wang; Qi-Gui Yan; Xiaobo Huang; et al. (Food and Chemical Toxicology, 2026)

Subchronic PM2.5 exposure exacerbates chronic stress-induced depression-like pathology in mice - Haoyu Lu; Xiaohui Zhao; Ran Ning; JunKoo Yi; Zhongmei He; Yan Zhao; Jianan Geng; Jia Zhou; Weijia Chen; Rui Du (Environmental Research, 2026)

Inner Helmholtz plane reconstruction-driven dynamic capture and conversion of crystalline water enables ultra-long cycle life of FeHCF cathodes - Rui Sun; Danyu Cui; Zijun Deng; Zhengyang Zhao; Zhe Cheng; Longqing Zhang; Yuhong Liang; Quanqiang Yuan; Chengcheng He; Yan Zhang; Qian Ning; Yang Ren; et al. (Chemical Engineering Journal, 2026)

Placental multi-omics profiling reveals breed-related molecular differences associated with porcine reproductive performance - Yan Li; Qiushi Wang; Sujun Zhao; Xiaocheng Li; Rui Liu; Jinling Zhang; Xiaohui Chen; Zhiping He; Jiangling Li (Animal Reproduction Science, 2026)

Enhanced water level fluctuations reduced the competitive advantage of cyanobacteria - Yan Chen; Rui Xia; Ruining Jia; Junde Ming; Kai Zhang; Jinghui Dou; Tianxiang Zhao; Xiang Li; Qin Zhang; Qi Zhang (Journal of Hydrology, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

From microstructural features to macroscopic properties: A multi-scale investigation on starch characteristics of global potato (Solanum tuberosum L.) germplasm resources - Kai Zhang; Yan Gao; Xiyue Ran; Huajian Xu; Yizhi Du; Mingren Yang; Ruijiang Chen; Rui Jiang; Yong Zhao; Shahid Ullah Khan; Binjia Zhang; Dianqiu Lv (Food Chemistry, 2026)

Cloud vertical structure features from two-year Ka-band cloud radar measurements in Hefei, East China - Xueliang Deng; Lu Li; Wenjing Shi; Dongyan He; Rui Dai; Yan Yan; Guangyuan Zhang; Shuwen Yuan; Liang Zhao (Atmospheric Research, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

A novel forest fire scenario deduction method based on belief rule base - Rui Zhao; Ning Wang; Wenguang Yan; Enhui Zhao (Natural Hazards, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Integrative multi-omics combined with molecular docking and molecular dynamics simulations elucidates the mechanism driving the transition from green notes to fruity aroma during musang king durian ripening - Zhongyan Li; Tianci Yan; Bin Xu; Xulu Luo; Yumei Ding; Wei Fan; Qin Qiao; Shaojie Yuan; Hui Guo; Meng Zhang; Yan Zhao; Rui Wang; et al. (Food Research International, 2026)

Effects of heat input on heat-affected zone of simultaneously welded cruciform fillet joints in Q550D and Q690D steels - Yize Gao; Xiao-Ling Zhao; Yan-Bo Wang; Rui Yan; Zhe Sun; Guo-Qiang Li (Engineering Structures, 2026)

Effects of dietary Portulaca oleracea L. aqueous extract on growth performance, intestinal health and intestinal microflora of common carp (Cyprinus carpio) - Jing-Tong Huang; Cong-Fu Liu; Yu-Shi Cai; Li-Fang Li; Hai-Tao Zhao; Yan-Ping Yang; Rui-Fang Wang (Animal Feed Science and Technology, 2026)

Flagged data of the Langmuir probes onboard Swarm satellites related extremely low plasma density environment - Yuhao Zheng; Chao Xiong; Gaofang Mi; Yuanqiang Zhao; Ziyuan Zhu; Artem Smirnov; Rui Yan (Advances in Space Research, 2026)

Self-powered electron transfer on single-atom dual-reaction center: Achieving high-efficiency catalysis in oxidant-free systems - Wen Song; Enyu Zhao; Qinyi Wang; Pijun Duan; Xuguang Li; Tao Yan; Yanxia Zhao; Rui Feng; Yunhui Zhang; Yuanyuan Qu; Xing Xu; Liangguo Yan (Water Research, 2026)

A sucrose–jasmonic acid feedback loop drives stem cell senescence in Arabidopsis - Yan-die Chen; Rui Zhang; Jing Yang; Zhong Zhao (Molecular Plant, 2026)

Tailoring Co3O4 grain size and oxygen vacancy distribution via precursor concentration for enhanced direct N2O decomposition - Lijing Fang; Yan Zhang; Zongxiang Yang; Caixia Liu; Qian Zhao; Rui Han; Qingling Liu (Journal of Environmental Chemical Engineering, 2026)

Carbon-supported nZVI mediates Fe oxides-DOM interactions to regulate Cd and As bioavailability in co-contaminated soils - Jianhua Guo; Yan Wu; Heng Zhang; Rui Wang; Yue Zhao; Xin Fan; Shuaitao Feng; Zuben Xu (Journal of Environmental Chemical Engineering, 2026)

Relationship of catalytic performance and catalyst structure evolution based on pressurized CH4-CO2 reforming reaction over carbon-supported Co-Ir alloy catalysts - Wen Tang; Jing-Pei Cao; Xiao-Yan Zhao; Dan Xie; Kai-Rui Luan; Chang-Jiang Li; Qi-Ming She; Tungalagtamir Bold (Fuel, 2026)

Influence of ecological factors on the accumulation of active substances in Camellia nitidissima - Xiao-Xia Zhao; Meng-Xue Su; Shuang-Shuang Li; Hui Gao; Guo-Yue Yan; Shu-Rui Wang; Yan-Yuan Bai; Yang-Jiao Xie (Plant Biosystems, 2026)

Coral-based reconstruction of interannual and decadal SST variability in the northern South China Sea during the mid-Holocene - Zhiheng Wu; Tingli Yan; Rui Tang; Ben Wang; Yanjun Mei; Ning Zhao (Geo-Marine Letters, 2026)

Low abundance microorganisms enhance soil multifunctionality by emphasizing fungal roles as mediated by plant biomass - Ze-Ying Zhao; Xiao-Bin Xiong; Peng-Yang Wang; Jia-Cheng Guo; Yinglong Chen; Hong-Yan Tao; Nan Chang; Cheng-Rui Bi; Yun-Lu Chen; Yuan Song; You-Cai Xiong (Applied Soil Ecology, 2026)

Mechanical Properties of Glycated Cracked Articular Cartilage Under Uniaxial and Cyclic Tensile Loading - Li-Lan Gao; Yi Fang; Xiang-Long Lin; De-Zhao Kong; Yan-Song Tan; Rui-Xin Li; Kai Sun; Chun-Qiu Zhang; Yanliuxing Yan (Annals of Biomedical Engineering, 2026)

Co/Mo dual-doped NiS nanoflakes as efficient and robust OER electrocatalysts for industrial-scale seawater electrolysis - Shuangyan Lin; Yunjuan Tao; Zhikun Xu; Longzhen Li; Xing-Yuan Chen; Rui Yan; Zhifeng Zhao (Fuel, 2026)

Centrifuge modeling of static liquefaction in completely decomposed granite fill slopes - Zhun Liu; Yu Zhao; Teng Liang; Fan He; Rui Zhang; Zhuang Yan; Daosheng Ling; Liangtong Zhan; Yunmin Chen (Engineering Geology, 2026)

Nanoflower-like Co3S4/FeOOH heterostructure enables efficient norfloxacin degradation via synergistic radical-non-radical PMS activation - Yuerong Zhou; Ming Yi; Yu Zhao; Rui Yang; He Yan; Xiuwen Cheng (ENGINEERING Environment, 2026)

CRISPR Epigenome Editing of IL1R1 Expression of Neurons that Innervate the Temporomandibular Joint or Knee Causes Reduced Sensitization to Osteoarthritic Environment - Joshua D. Stover; Robby D. Bowles; Yenisel Cruz-Almeida; Robert M. Caudle; Kyle D. Allen; Armen Akopian; Benjamin Arenkiel; Basak Ayaz; Yangjin Bae; Bruna Balbino de Paula; Anita Bandrowski; Mario Danilo Boada; et al. (Annals of Biomedical Engineering, 2026)

Antimicrobial polyketides from an endophytic fungus Arcopilus aureus HJ-7 from Ardisia mamillata Hance - Li-Qi Liang; Xian-Hua He; Chun-Yan Wei; Jing-Xian Zhao; Qian Wu; Min Liang; Jun Li; Yan Luo; Wei-Feng Xu; Rui-Yun Yang (Natural Product Research, 2026)

Quantitative study on the cave environmental factors for the fractionation of stable oxygen isotopes during the deposition of speleothem - Yue Jin; Chun-Jie Wang; Jian Zhang; Wen-Jun Sun; Chao-Jun Chen; Yao Wu; Hua-Yan Li; Yue-Hua Xiang; Yue-Yuan Lin; Xin-Rui Ye; Xin-Yan Li; Zhong-Lin Deng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

A phycospheric bacteria perspective: Preliminary investigation into the differential formation of sporangial branchlets in Pyropia haitanensis under varied temperatures and light intensities - Rui Zhao; Rui Chai; Qingli Gong; Ningning Xu; Wenjie Yan; Xu Gao (Marine Environmental Research, 2026)

Tailoring the microenvironment of ruthenium centers at poly(ionic liquid) frameworks for mild reverse water gas shift reaction - Rui Wang; Yi-Ran Du; Jia-Ni Li; Jing-Wen Sun; Zhao-Rong Yan; Bao-Hua Xu (Chemical Engineering Journal, 2026)

Spatiotemporal relationships between mammal habitat suitability and recreational hiking intensity in Xiaowutaishan National Nature Reserve, China - Ming Yam Chan; Yue Cao; Zhicong Zhao; Pei Wang; Yunshuang Feng; Le Yu; Steve Carver; Xuehua Liu; Ruijia Zhu; Fengze Lin; Xialin Li; Yiqing Wang; et al. (Biological Conservation, 2026)

Twelve-year organic substitution fertilization mitigates microbial nutrient limitation and enhances soil carbon pool stability in a rubber plantation - Wenxian Xu; Yingying Zhang; Wenjie Liu; Congju Zhao; Ashar Tahir; Chuan Yang; Xinwei Guo; Rui Sun; Xiangshuai Yan; Huifang Yuan; Qiu Yang; Zhixiang Wu (Plant and Soil, 2026)

Modeling and experimental validation of crack-induced bottom-side erosion effects in buried pipelines - Yan-Ning Wang; Tai-Kai Li; Jing-Rui Peng; Xin-Hao Min; Lin-Shuang Zhao (Tunnelling and Underground Space Technology, 2026)

Effects of mung bean addition on quality and starch anti-digestion mechanism of oat noodles - Rui-xian Shang; Wei-feng Zhang; Zi-hao Tu; Xiu-juan Ren; Yan-xia An; Gui-Hong Yin; Jian Zhang; Yang Zhao (Journal of Cereal Science, 2026)

pH-responsive dual MOF-on-MOF core-shell nanocarrier enables an innovative “pesticide–fertilizer integration” strategy for advanced plant disease management - Yingjian Ma; Pengkun Yan; Xiangdong Li; Meng Yu; Shouhe Pan; Yinmin Wang; Rui Zhao; Xinyu Guo; Yucheng Gu; Yong Xu; Xuemin Wu (Chemical Engineering Journal, 2026)

Interfacial charge threshold induced high-safety energetic co-particles - Hao-Rui Zhang; Yingqi Mao; Minghui Dai; Djalal Trache; Xu Zhao; Zhijian Yang; Qi-Long Yan (Chemical Engineering Journal, 2026)

Non-enzymatic glycation modifies the functional properties and extends the application of poultry egg proteins - Rui Wang; Shuping Chen; Yao Yao; Na Wu; Yan Zhao; Lilan Xu; Mingsheng Xu; Yonggang Tu (Critical Reviews in Food Science and Nutrition, 2026)

Quantifying the critical regulator role of irradiation-enhanced electric field in nanoplastics aggregation with heavy metals - Yaowu Zhang; Xianzheng Yuan; Ying Tang; Xinmin Liu; Fengxin Zhao; Yan Peng; Xinping Gao; Lin Wang; Lijing Wang; Rui Tian; Rui Li; Hang Li (Water Research, 2026)

Corrigendum to “Silica nanoparticles induce cardiac injury and dysfunction via ROS/Ca2+/CaMKII signaling” [Sci. Total Environ., 837 (2022), 155733] - Yi Qi; Hailin Xu; Xueyan Li; Xinying Zhao; Yan Li; Xianqing Zhou; Rui Chen; Yanbo Li; Zhiwei Sun; Caixia Guo (Science of The Total Environment, 2026)

Modern pollen analysis on peatlands across monsoonal China and its implications for reconstruction - Shu Chen; Mengmeng Wang; Chunmei Ma; Tianyi Tang; Rui Ke; Jiaming Hou; Xinrong Zhang; Zhuo Zheng; Xiayun Xiao; Yan Zhao; Huayu Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Mitophagy dynamics during oxidative to reductive stress shift potentiates arsenite-induced malignant transformation potential in human keratinocytes - Qianlei Yang; Xingrun Li; Qi Kong; Yuqi Yang; Haixuan Xia; Rui Yan; Xiaoyun Zhang; Hui Lu; Ting Zhang; Chen Zhao; Bohan Xu; Koichi Kato; et al. (Journal of Hazardous Materials, 2026)

Deciphering the potential risks of Yersinia enterocolitica across multi-points in food chain: prevalence, biofilm, and cross-stage transmission routes - Zhiguo Fang; Juran Mao; Zongzong Chen; Yue Wu; Xueqin Zhao; Rui Tian; Ye Lv; Xiao Xiao; Jiaqi Yan; Xiuqin Lou; Jun Li (Food Research International, 2026)

Interfacial proton transfer in MOF-functionalized aerogel enabling for selective heavy metal adsorption - Jun-Heng Fu; Baihang Cai; Yeshuang Zhong; Xinru Gong; Shuangfeng Fang; Fei Wang; Yufeng Yan; Rui Dai; Puyuan Liu; Jianye Gao; Ruihan Wang; Ying Cao; et al. (Desalination, 2026)

Quantifying glacier and snow shrinkage: future water stress in Northern Tien Shan, Central Asia - Qiudong Zhao; Yongjian Ding; Zizhen Jin; Yan Qin; Rui He; Donghui Shangguan; Shiqiang Zhang; Yaping Chang; Haidong Han (CATENA, 2026)

Understanding the migration and transformation characteristics of Cr3+ in the hydrothermal cracking of biomass model components - Rui Xia; Kai-le Li; Peng Zhao; Xiao-xiao Yang; Jue Wang; Ke-wen An; Qing-hai Li; Hui Zhou; Yan-guo Zhang (Biomass and Bioenergy, 2026)

Phosphorus fertilization shapes rhizosphere beneficial microbial communities and soil–plant relations in arid cotton fields of Xinjiang, China - Bin Peng; Shuai Zhao; Cong-Rui Liu; Wen-Xuan Mai; Na Zhou; Ping Zhang; Shu-Ying Wang; Xu Liu; Bao-Zhan Wang; Chang-Yan Tian (Plant and Soil, 2026)

Non-degenerate and degenerate soliton solutions to the semi-discrete vector nonlinear Schrödinger system - Yang-Yang Du; Yan-Nan Zhao; Hui-Qin Hao; Rui Guo; Jian-Wen Zhang (Wave Motion, 2026)

GABPα2β2 tetramer deficiency impairs natural killer cell maturation, compromising cytotoxicity and resistance against melanoma - Weiwei Jia; Wanting Zhong; Shanshan Hao; Zhao Wang; Shuaishuai Niu; Yingdi Xu; Yajiao Zhang; Mingxia Feng; Haitao Jiang; Jiarui Zhang; Danli Song; Peiyao Yan; et al. (Science Bulletin, 2026)

Biaxially oriented polyethylene film packing and hydrogen sulfide fumigation maintain postharvest quality of tomato fruits by reducing malondialdehyde levels and water loss - Le-Ying Yan; Pedro Garcia-Caparros; Jia-Xin Wang; Wan-Ken Chen; Xiong-Jie Wu; Dong-Bo Zhu; Rui Zhang; Zhao-Zhong Wang; Hua Zhang; Gai-Fang Yao (Postharvest Biology and Technology, 2026)

Dietary components cooperate with intestinal flora to regulate food allergy - Jiaxi Yan; Li Niu; Wei Wang; Rui Gao; Jianxiong Hao; Huan Rao; Dandan Zhao; Xueqiang Liu; Wentong Xue; Yang Tian (Food Chemistry, 2026)

Automatic Image Co-registration of Carotid Angiography and Intravascular Optical Coherence Tomography Based on Machine Learning Method: A Pilot Feasibility Study - Hui Xu; Jia-Nan Li; Yan Xu; Jun-Ren Ma; Kang Zong; Rui Zhu; Yi-Hui Cao; Peng-Fei Yang; Rui Zhao; Jian-Min Liu (Annals of Biomedical Engineering, 2026)

Strategic sampling for training a semantic segmentation model in operational mapping: Case studies on cropland parcel extraction - Rui Lu; Ronghua Liao; Ran Meng; Yingchu Hu; Yi Zhao; Yan Guo; Yingfan Zhang; Zhou Shi; Su Ye (Remote Sensing of Environment, 2025)

Seismic facies identification using a U-KAN network with multi-scale spatial pyramid attention mechanism - Binpeng Yan; Mutian Li; Rui Pan; Jiaqi Zhao (Journal of Applied Geophysics, 2025)

Point-of-care testing of neuromyelitis optica spectrum disorder using a sonochemically enhanced bifunctional CdTe-ZIF-8 nanohybrids-labelled lateral flow immunoassay - Qing Fu; Manxia Wang; Jia Shu; Guangjun Xiao; Zhujun Ai; Xin Gao; Huan Cai; Yan Zhao; Xuhuai Fu; Zhizhong Li; Mengjie Zhang; Jinzhou Feng; et al. (Chemical Engineering Journal, 2025)

Superacid polymer electrolyte with end-group-protected proton sites mitigates ammonia poisoning for efficient electrochemical hydrogen separation from ammonia cracking reformate gas - Jiaqi Shuai; Hao Li; Zhengrui Xiao; Zeqi You; Yucong Liao; Rui Wang; Yafeng Li; Yuanwei Yan; Jiangping Song; Tian Tian; Lan Zhang; Siew Hwa Chan; et al. (Chemical Engineering Journal, 2025)

Dual pH/glutathione-responsive polyphenol-based self-assembled nanoparticles loaded with lambda-cyhalothrin show enhanced UV stability and non-target organism safety - Lei Wang; Zheng Zhang; Yu Fang; Rui Zhao; Shouhe Pan; Meng Yu; Yinjie Ma; Yinmin Wang; Xiquan Ding; Xinyu Guo; Fengyu Li; Pengkun Yan; et al. (Chemical Engineering Journal, 2025)

MXene triggers room-temperature 4D printing of advanced ionic hydrogels for sensitive electronic skin - Qinglong He; Chendong Zhao; Yuanjie Jiang; Jimei Liu; Xinyu Liu; Rui Jia; Cheng Yang; Mengzhou Liao; Yan Zhao; Desheng Kong; Valeria Nicolosi; Caofeng Pan; et al. (Chemical Engineering Journal, 2025)

Impact of thallium contamination on microbial communities and biogeochemical cycles in freshwater ecosystems - Shuang Yan; Yongxin Bing; Qianli Ma; Rui Zhao; Xiaodie Cai; Yuyin Yang; Sili Chen; Shuguang Xie (Aquatic Ecology, 2025)

Deep structure of the middle segment of the Bangong-Nujiang Suture Zone based on aerogravity and aeromagnetic anomalies, Qinghai-Tibet Plateau - Bao-bao Cao; Dao-qing Zhou; Yan-yan Wei; Rui Zhao; Qiao-juan Yan; Lei Xu; Di-shuo Zhang (Applied Geophysics, 2025)

P T symmetry preserving, symmetry breaking and propagation behaviors in degenerate and non-degenerate solitons beyond the nonlocal Manakov system - Yang-Yang Du; Yan-Nan Zhao; Rui Guo; Jian-Wen Zhang (Wave Motion, 2025)

Lipophilic marine toxins effects on Neuro-2a, NG108-15 and MCF-7 cell lines - Rui Zhao; Lei Han; Peipei Zhang; Yan Zhang; Yusheng Shi; Yubo Liang (Toxicon, 2025)

Populus euphratica PeMAX2 counteracts PeGRP2 to stabilize target mRNAs relating to salt tolerance - Jing Li; Jun Yao; Siyuan Ma; Jian Liu; Ziyan Zhao; Zhe Liu; Kexin Yin; Caixia Yan; Kaiyue Dong; Rui Shi; Nan Zhao; Rui Zhao; et al. (Plant Science, 2025)

Be–Nb–Ta mineralization in granites: An example from the Nyalam area in the Himalayan belt, southern Tibet - Li-E Gao; Lingsen Zeng; Linghao Zhao; Lilong Yan; Yinglong Di; Guangxu Li; Yaying Wang; Rui Wang; Li Wang (Lithos, 2025)

Dual-stage reverse-dialysis-engineered cartilage-biomimetic hydrogels: Highly resilient anti-swelling double-layer architectures - Zheng-Feng Zhang; Mei-Yan Ling; Xiao-Rui Ge; Jia-Ying Chen; Bei Zhang; Xiao-Hui Yao; Peng Song; Wei-Guo Zhao; Dong-Yang Zhang; Jun Wang (Chemical Engineering Journal, 2025)

Garnet dissolution–reprecipitation processes in leucogranitic magma and their profound geochemical consequences - Rui Wang; Li-E Gao; Lingsen Zeng; Lilong Yan; Linghao Zhao; Guyue Hu; Li Wang; Haitao Wang (Chemical Geology, 2025)

Human influence on summer wetting in Northwest China from 1961 to 2014: Roles of greenhouse gases and anthropogenic aerosols - Rui He; Yan Guo; Buwen Dong; Neng Luo; Zihui Zhao; Zhibo Gao (Atmospheric Research, 2025)

Timosaponin B- II Enhances Osteogenic Differentiation of Human Periodontal Ligament Stem Cells via PI3K/AKT/GSK3β Signaling Pathway - Dai-Wei Yang; Xiao-Bin Cui; Rui Dong; Zhao-Yan Wu; Yu-Xing Zhang; Peng Yang; Jun Zhang (Stem Cell Reviews and Reports, 2025)

The Reliability of Offshore Jacket Platforms Based on Bayesian Calibration - Fang Zhou; Fansheng Meng; Yuhan Zhao; Jinbo Chen; Rui Zhao; Yongfei Zhang; Zhaolong Han; Yan Bao (Journal of Marine Science and Engineering, 2025)
The safety of offshore structures is a key topic in developing offshore oil and gas and offshore wind energy. Due to the harsh offshore environment and costly offshore field tests, offshore field trials to validate the theoretical models for offshore structures are limited, and testing results can rarely be found in the public domain. The Bayesian updating technique combines existing engineering knowledge with the observed performance data about in-service offshore structures to update model uncertainties. Hence, the Bayesian technique overcomes the shortcomings of limited offshore field trials. This paper compiles performance data on offshore jackets in hurricanes in the Gulf of Mexico (GoM) in the past two decades and calibrates the model uncertainties of the API method using the Bayesian technique. With the updated model uncertainty, this paper evaluates the reliability of generic offshore jackets in the GoM and the case study’s offshore wind substation in China. With a typical reserve strength ratio (RSR) of about 2.0 to 2.2, the reliability analysis reveals that the updated annual failure probability of a generic offshore jacket in the GoM is largely less than 1.0×10−3, indicating that the extreme weather overload is not a major concern. However, the RSR of the case study platform in China is greater than 4.5, and the annual failure probability for the case study offshore wind substation is about 2–3 orders of magnitude lower than typical oil and gas jackets. Hence, from the extreme metocean condition perspective, the substation under investigation has sufficient structural capacity, and the design practice for offshore wind substations in northern China may be improved.

3D seismic fault identification using two-branch network with a lightweight attention mechanism - Binpeng Yan; Rui Pan; Jiaqi Zhao; Mutian Li (Acta Geophysica, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Assessment of environmental and health impacts during 3D printing of candidate polymeric materials for space additive manufacturing - Junling Li; Yi Liu; Chao Peng; Qifan Liu; Wei Zhao; Mingyuan Liu; Xinyu Du; Yongyin Yan; Yufei Song; Kaihui Xia; Chun Chen; Haijie Zhang; et al. (Journal of Hazardous Materials, 2025)

SIRT3 promotes mitophagy to attenuate fumonisin B1-induced chicken hepatocyte senescence and antagonism of lycopene - Yuan-Hang Chang; Ming-Shan Chen; Hong-Mei Zhu; Rui-Qi Liu; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yue Cheng; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Recent research progress of methane dry reforming to syngas - Yan Wang; Rui Li; Chunyang Zeng; Wenjuan Sun; Hui Fan; Qingxiang Ma; Tian-Sheng Zhao (Fuel, 2025)

Enhanced moisture tolerance and toluene oxidation activity of δ-MnO2 catalysts by Sn doping: Phase transition and surface protection - Yiming Li; Mengxia Xu; Rui Liu; Shuibo Wang; Taotao Sun; Zijun Yan; Cong Wan; Hongbo Yu; Haocheng Li; Haotian Li; Xudong Zhao; Kaijie Li; et al. (Fuel, 2025)

Study on the reaction mechanism of nitrogen-containing gases from polyurethane pyrolysis with carbonate molten salts - Yang-Hai Zheng; Jun-Qiang Rui; Sheng-Rong Guo; Cheng Yao; Zhao-Yang Liu; Yun Xue; Ju-Yue Yang; Yong-De Yan (Fuel, 2025)

Sunlight-activated photochromic-photothermal nanofibrous textiles for self-monitored thermal management - Shuai Liang; An-Yang Duan; Shi-Kun Yan; Yan-Rui Zhao; Jin Zhang; Guo-Wei Xiao; Chang-Hai Xu; Ji-Xiang Hu; Guo-Ming Wang (Chemical Engineering Journal, 2025)

Bioinspired conductive-catalytic network accelerates rate-determining steps at cathode-electrolyte interface for high-loading Li-S batteries - Cai-Yun Zhang; Chen-Yang Wang; En-Zhu Zhao; Guowei Yu; Hui-Ling Deng; Rui Huang; Zhao-Yun Wang; Pu Hu; Min Yan; Zhitian Liu (Chemical Engineering Journal, 2025)

Particle size fractionation treatment for sustainable remediation of field-contaminated soil - Likun Zhao; Shiyu Wang; Rui Yue; Ye He; Akram N. Alshawabkeh; Yuewei Yang; Shupeng Li; Yan Li; Chaoqi Chen; Hua Li; Xuhui Mao (Chemical Engineering Journal, 2025)

Probabilistic assessment of response spectra for multiple damping levels in seismic hazard analysis - Haizhong Zhang; Rui Zhang; Yan-Gang Zhao; Hongjun Si; Haixiu Zhang (Soil Dynamics and Earthquake Engineering, 2025)

An overview of extreme weather-epidemic compound disasters - Jianping Huang; Xinbo Lian; Huijun Wang; Tong Zhu; Han Li; Yingjie Zhao; Rui Wang; Danfeng Wang; Wei Yan; Shujuan Hu; Xiaodan Guan; Shanshan Wang (Science Bulletin, 2025)

Engineering B₄O₇2−-cross-linked double‑carbon layer separators for mitigating molecular shuttle in rechargeable small-molecule batteries - Xinyu Wang; Rui Li; Guoqing Zhao; Xiaorong Yan; Mingsheng Yang; Bei Wang; Haiping Yu; Mengxiao Li; Yuxin Hao; Zhihui Wang; Jingru Liu; Mingjun Hu; et al. (Chemical Engineering Journal, 2025)

Conduction of AgNPs with different surface charges in pine trees and their prevention and control of pine wood nematode disease - Shouhe Pan; Pengkun Yan; Rui Zhao; Fengyu Li; Lei Wang; Yinmin Wang; Ze Lv; Yingjian Ma; Meng Yu; Xinyu Guo; Yonggang Xia; Yong Xu; et al. (Chemical Engineering Journal, 2025)

Spatial confinement of Bi/TiO2 nanoparticles with an abundant heterointerface in hollow carbon spheres for durable sodium storage - Zhao Li; Rui Yuan; Yangwu Hou; Xinde Wei; Zhaozhao Zhu; Yamei Wang; Shilong Xu; Lei Chen; Yan Wang; Rui Wu; Qingquan Kong; Jun Song Chen (Chemical Engineering Journal, 2025)

Properties of rich-Nae effect and reversible oxygen redox with a complete solid-solution sodium-storage behavior - Wei Zhao; Shao-Hua Luo; Yicheng Lin; Guodong Hao; Rui Huang; Pengyu Li; Ge Wang; Jun Cong; Shengxun Yan; Lixiong Qian (Chemical Engineering Journal, 2025)

Xylem hydraulic impairment due to stronger drought stress accounts for the reduced crown vitality and growth performance of Mongolian pine trees in higher-density plantations - Xue-Wei Gong; Yi-Lei Ouyang; Yan-Yan Liu; Jin-En Zhang; Zhao-Kui Li; Hong-Li Li; Zhuo-Qun Fang; Yu Cao; De-Dong Wu; Qiu-Rui Ning; Guang-You Hao (Agricultural and Forest Meteorology, 2025)

Cadmium induces autophagy via IRE1 signaling pathway activated by Ca2 + in GC-2spd cells - Yue Han; Juan Dai; Jinxin Cheng; Yan He; Chengkun Zhao; Rui Li; Yaqin Zhang; Ling Zhang; Ting Zhou; Yuqin Shi (Reproductive Toxicology, 2025)

Multi-target directed ligands design of 1-O-Acetylbritannilactone derivatives: Dual anti-neuroinflammatory and acetylcholinesterase inhibitory activities - Yan-Peng Liang; Qian Gao; Hong Chen; Rui Ma; Xiao-Bo Zhao; Xiao-Jie Jin; Jian Zhang; Yan-Ping Shi; Wei Ha (Phytochemistry Letters, 2025)

TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Efficient in-situ transfer hydrogenation of palmitic acid into alkanes over Ni/CexZr1-xO2 solid solution catalysts in aqueous medium with methanol as the hydrogen donor - Yuhao Yan; Daxin Jiang; Rui Li; Jie Zhao; Rumin Zheng; Xianliang Song; Yulong Wu (Fuel, 2025)

Climate-driven spatiotemporal variation of soil erodibility in China - Lili Qu; Zheng Sun; Zhiyuan Tian; J.M. Schoorl; Rui Ma; Yan Zhao; Yihang Wu; Yin Liang (Environmental Impact Assessment Review, 2025)

Functional nucleic acid-stabilized selenium nanotechnology enable synergistic healing of diabetic chronic wounds - Si-Wei Yang; Jing Wang; Yan Tan; Xiao Jing; Chen-Yu Wang; Zhi-Li Yao; Wen-Hui Wang; Yong-Ji Li; Hao-Rui Li; Yan Zhao; De-Ming Kong; Qi-Liang Cai (Chemical Engineering Journal, 2025)

Electroacupuncture may alleviate inflammatory pain by downregulating the expression of P2Y14 receptor in the primary somatosensory cortex - Shuai Hou; Cui-Yuan Chen; Rui-Zhu Zhou; Liu-Xuan He; Xiao-Xiao Zhao; Sha-Sha Chen; Sha Yang; Hai-Yan Yin; Shu-Guang Yu (Purinergic Signalling, 2025)

A unified probabilistic assessment of multiple ground-motion intensity measures in seismic hazard analysis based on Fourier amplitude spectra - Haizhong Zhang; Yan-Gang Zhao; Rui Zhang; Hongjun Si (Bulletin of Earthquake Engineering, 2025)

Preparation, structure and activity determinations of novel immunomodulatory peptides from Limnospira platensis - Chen Zhao; Tingxin Zhang; Shunan Ma; Rui Deng; Liping Zhu; Shigan Yan (Algal Research, 2025)

A new perspective on iron-dependent cell death: PRDX-1-mediated ferroptosis in tumor cells - Rui Li; Zhiyuan Wang; Yueyue Yujiang; Mengyuan Hu; Hongkun Zhao; Fei Yan (Apoptosis, 2025)

Comparative analysis of phycospheric microbial diversity and metabolome between vegetative and matured conchocelis of Pyropia haitanensis - Rui Zhao; Zenghu Zhang; Fuli Liu; Qikun Xing; Ningning Xu; Wenjie Yan; Xu Gao (Aquaculture, 2025)

Genome-wide characterization of soybean bile acid: sodium symporter genes reveals a positive role of GmBASS2-2 in salt stress response - Xunchao Zhao; Yan Zhang; Yuan Li; Xiuli Rui; Jie Wang; Yuhang Zhan; Yongguang Li; Xue Zhao; Yingpeng Han (Theoretical and Applied Genetics, 2025)

Corrigendum to “Evaluation of the main economic characteristics of a narrow-thallus strain of Neoporphyra haitanensis” [Aquaculture Volume 558: 738395, 15 September 2022] - Rui Zhao; Yan Xu; Kai Xu; Dehua Ji; Changsheng Chen; Wenlei Wang; Chaotian Xie (Aquaculture, 2025)

Impact of soil erosion-driven degradation on crop yield in black soils of Northeast China's Songnen Plain - Yan ZHAO; Zhiyuan TIAN; Rui MA; Lili QU; Yihang WU; Yin LIANG (Pedosphere, 2025)

The long noncoding RNA VIVIpary promotes seed dormancy release and pre-harvest sprouting through chromatin remodeling in rice - Lu Yang; Yu Cheng; Chao Yuan; Yan-Fei Zhou; Qiao-Juan Huang; Wen-Long Zhao; Rui-Rui He; Jie Jiang; Yi-Chao Qin; Zheng-Tong Chen; Yu-Chan Zhang; Meng-Qi Lei; et al. (Molecular Plant, 2025)

Corrigendum to “N-doped carbon dots/g-C3N4 photoexcitation simultaneously enhanced the microbial degradation of nitrate and oxytetracycline in a low C/N ratio aquaculture wastewater” [Chem. Eng. J. 491 (2024) 151763] - Pin Peng; Lixiang Chen; Xinyu Yan; Rui Bai; Bob Adyari; Xudong Zhou; Feng Zhao (Chemical Engineering Journal, 2025)

pH/GSH-Driven inside-out nanoreactor initiating copper(I)-precursor chelation-promoted bioorthogonal therapy - Zhexiang Wang; Xinyi Li; Rui Lv; Ruochen Guo; Qinglei Shu; Tianjin Ge; Jun Yan; Zhihao Zhao; Guanghui Wang; Jian Liu (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Identification of Age-Related Characteristic Genes Involved in Severe COVID-19 Infection Among Elderly Patients Using Machine Learning and Immune Cell Infiltration Analysis - Huan Li; Jin Zhao; Yan Xing; Jia Chen; Ziying Wen; Rui Ma; Fengxia Han; Boyong Huang; Hao Wang; Cui Li; Yang Chen; Xiaoxuan Ning (Biochemical Genetics, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Multi-omics analysis reveals the role of L-Glutamate in regulating cold tolerance of postharvest prune fruit - Yuanyuan Hou; Wanyu Yan; Rui Deng; Jiayi Wang; Yu Wang; Liang Wang; Jun Xing; Peng Jin; Yating Zhao (Postharvest Biology and Technology, 2025)

Intergenerational transfer of micro(nano)plastics in different organisms - Yanhui Dai; Rui Han; Zhiming Yao; Han Yan; Zhuomiao Liu; Xia Liu; Tongtao Yue; Jian Zhao; Zhenyu Wang; Baoshan Xing (Journal of Hazardous Materials, 2025)

Quantification of water-soluble moroxydine hydrochloride residue using UPLC-MS/MS: Development and validation in 22 different complex plant-based food samples - Rui Zhang; Xuan Zhu; Liqian Chen; Yan He; Min Zhao; Bing Qian; Bingjun Han (Food Chemistry, 2025)

Low-damage performance of rocking column bases with Belleville Springs for enhanced seismic resilience - Jiang-Yue Xie; Zhenduo Yan; Junrong Liu; Rui Zhang; Ping Xiang; Xianzhong Zhao; Gregory A. MacRae; G. Charles Clifton; Rajesh P. Dhakal; Shahab Ramhormozian; Geoffrey Rodgers; Pierre Quenneville; et al. (Engineering Structures, 2025)

Fabrication of flexible polymer-MOF composite electrolyte for solid-state lithium metal batteries with high rate performance - Jiansheng Gao; Yan Chai; Jialun Ni; Yong Zeng; Gaoyuan Zhang; Xueling Liu; De Ning; Xinghui Jin; Huajun Zhao; Dong Zhou; Rui Gao; Wei Wu; et al. (Chemical Engineering Journal, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Identification and fungicide sensitivity of Fusarium oxysporum, the cause of Fusarium wilt on Codonopsis pilosula in Shanxi Province (Lu Dangshen), China - Yan Wang; Dainan Hao; Haozhe Jiang; Zhaoxiong Fei; Rui Zhao; Jiaxin Gao; Guangxin Li; Chunwei Wang (Crop Protection, 2025)

Regulating gypsum scaling-induced wetting in membrane distillation by heterogeneous crystallization: Role of filter media - Haiqing Chang; Zeren Ma; Huaxin Zhao; Dan Qu; Caihong Liu; Zhongsen Yan; Rui Li; Fangshu Qu; Heng Liang; Radisav D. Vidic (Water Research, 2025)

Correlation of lipid hydrolysis, oxidation, and molecular transformation with volatile compound revolution in pork during postmortem wet-aging process - Kaihua Zhang; Rui Hao; Shouwei Wang; Zheqi Zhang; Dan Li; Xiaoman Li; Bing Zhao; Shunliang Zhang; Yan Zhao; Xiangning Chen (Food Chemistry, 2025)

Identification and characterization of anthocyanins’ composition and regulatory genes involved in anthocyanins biosynthesis in water dropwort (Oenanthe javanica) - Kai Feng; Nan Sun; Ya-Qing Bian; Wu-Di Rui; Ya-Jie Yan; Zhi-Yuan Yang; Jia-Lu Liu; Zi-Qi Zhou; Shu-Ping Zhao; Peng Wu; Liang-Jun Li (Planta, 2025)

Microrna363-5p targets thrombospondin3 to regulate pathological cardiac remodeling - Yu-kun Ma; Xin-yi Han; Shu-huai Zan; Hui-ting Liu; Xue-yan Zhou; Dan-xue Zhao; Rui Xing; Peng Zhao (Molecular and Cellular Biochemistry, 2025)

A self-powered PFC sensing platform via integrating aptamer-modified photoanode and Z-scheme signal amplifying photocathode for microcystin-LR detection - Ying Wang; Yuyi Wang; Lijun Wang; Rui Feng; Meng Sun; Yanxia Zhao; Tao Yan; Qin Wei (Analytica Chimica Acta, 2025)

Pharmacologically activating BDNF/TrkB signaling exerted rapid-acting antidepressant-like effects through improving synaptic plasticity and neuroinflammation - Si-Rui Sun; Jia-Ning Zhao; Peng-Wei Bi; Hui-Ying Zhang; Guang-Xiang Li; Jiao-Zhao Yan; Yun-Feng Li; Yong-Yu Yin; Hao Cheng (Metabolic Brain Disease, 2025)

Molecular identification of three cytochrome P450 genes and their potential roles in insecticides tolerance in Grapholita molesta (Busck) - Hui Han; Ming-Gao Li; Kai-Yang Xing; Qi Wang; Jun Hu; Zhi-Guo Zhao; Qin Yu; Rui-Yan Ma; Ling-Ling Gao; Yan-Qiong Guo (Pesticide Biochemistry and Physiology, 2025)

Soil organic carbon dynamics (2008–2020) across different cultivated land use types in a subtropical region - Jianming Li; Siqi Li; Rui Zhao; Shihe Xing; Hanyue Chen; Yan Huang; Liming Zhang; Jing Li (Geoderma Regional, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Investigation on neutronics changes in tungsten granular blockage accident on VENUS-II light water reactor - Liang Chen; Wei Jiang; Zhao-Dong Xia; Fei Ma; Rui Yu; Hai-Yan Meng; Qi Zhou; Hong-Lin Ge; Yan-Bin Zhang; Xue-Ying Zhang (Annals of Nuclear Energy, 2025)

Forest Microclimate as a Driver of Epiphytic Bryophyte Diversity Along a Subtropical Elevational Gradient - Zun Dai; Shi‐chen Xing; S. Robbert Gradstein; Min Li; Shu‐wen Tu; Xing Chen; Xue Yao; Shuang Gao; Rui‐ping Shi; Lu‐yan Tang; Ran Zhang; Zhao‐chen Zhang; et al. (Journal of Biogeography, 2025)
Aim Considering the importance of microclimate in maintaining the diversity of epiphytic bryophytes, we investigated epiphytic bryophytes along an elevational gradient in the subtropical forest of eastern China to unravel the diversity patterns of epiphytic liverworts and mosses along the elevational gradients and the roles of forest microclimates, topographic variables and host plant composition attributes in shaping these elevational diversity patterns. Location Tianmushan National Nature Reserve, Zhejiang, China. Taxon Epiphytic bryophytes. Methods Species diversity patterns of liverworts and mosses were compared based on an inventory of 16 plots along an elevational gradient from 367 to 1470 m. In situ microclimatic data of air temperature and moisture were collected under constant monitoring for over 3 years. Spatial linear models and structural equation models were used to assess the relative roles of the environmental variables in shaping the patterns of species diversity along elevation. Results We found that epiphytic liverwort and moss richness showed different elevational patterns; overall richness patterns of epiphytic bryophytes were largely driven by mosses. Epiphytic mosses exhibited a decline, followed by a hump‐shaped pattern of species richness with increasing elevation, while epiphytic liverworts showed a mid‐elevation plateau with a richness maximum between 800 and 1300 m. Forest microclimate, topography and host plant composition attributes influence epiphytic moss and liverwort patterns differently and interact in a complex way. Overall, species richness of epiphytic liverworts was most strongly affected by microclimate (mean annual air temperature of growing season) and of epiphytic mosses richness by topography (slope). Further, epiphytic liverwort species richness was more influenced by temperature than moisture. Main Conclusions This study highlights the importance of collecting climatic factors at a fine scale (microhabitats) for understanding the patterns and drivers of bryophyte diversity. Further, our findings demonstrate the differences between liverworts and mosses in terms of their response to different environments in the forest ecosystem.

Ancient genomes shed light on the long-term genetic stability in the Central Plain of China - Hao Ma; Yawei Zhou; Rui Wang; Fei Yan; Haodong Chen; Limin Qiu; Jing Zhao; Li Jin; Chuan-Chao Wang (Science Bulletin, 2025)

Efficient removal of cationic malachite green using co-pyrolyzed corn straw biochar-montmorillonite composites - Xiaodong Yang; Zhiyong Hou; Xuefei Yang; Minghui Li; Yuanxia Guo; Kai Wang; Shuaiqi Luo; Jin Zhao; Pengkai Sun; Qiang Yang; Rui Chen; Yan Yan; et al. (Journal of Environmental Management, 2025)

Roles of S100A1 and S100A10 from hybrid grouper (Epinephelus lanceolatus♂ × Epinephelus fuscoguttatus♀) in immune response to Vibrio infection - Sheng Yuan; Ying Huang; Quan Wang; Yan Shi; Xiao-Rui Song; Zhe Zhao (Fish & Shellfish Immunology, 2025)

Highly electrostatic cellulose acetate materials assisted by copper ion coordination for air filtration - Ning Yan; Ting Gao; Li Hua; Fan Xie; Rui-Xin Liu; Ding-Gen Hu; Zhao-Qing Lu (Chemical Engineering Journal, 2025)

Ultrafast and ultrastable Na-ion storage in interface engineered MoS2/MXene nanohybrids with nanoconfinement for high-performance sodium-ion capacitors - Yuanhua Xiao; Qingling Le; Yang Kong; Wendi Lv; Dangcheng Su; Xianhong Rui; Shuyan Yu; Aiqing Zhang; Junhong Zhao; Qingxiang Yang; Qingxian Jin; Yujie Zheng; et al. (Chemical Engineering Journal, 2025)

Grid shielding of interphase hybrids via spatial charge separation for regulating interfacial Zn redox kinetics - Ke Chen; Kun Rui; Wenhao Si; Huinan Wang; Cong Zhao; Yan Yan; Huijuan Lin; Jixin Zhu (Chemical Engineering Journal, 2025)

The long noncoding RNA ALEX1 confers a functional phase state of ARF3 to enhance rice resistance to bacterial pathogens - Meng-Qi Lei; Rui-Rui He; Yan-Fei Zhou; Lu Yang; Zhen-Fei Zhang; Chao Yuan; Wen-Long Zhao; Yu Cheng; Jian-Ping Lian; Yu-Chan Zhang; Wen-Tao Wang; Yang Yu; et al. (Molecular Plant, 2025)

Effective removal of Pb from industrial wastewater: A new approach to remove Pb from wastewater based on engineered yeast - Hao Luo; Zheng Su; Yang Liu; Dong-Fang Yuan; Rui Wang; Yu-Hang Ning; Dong-Jiao Zhang; Xian-Ke Chen; Zhao-Bao Wang; Xue-Yan Gao; Yue-Chao Zhang; Guang Cheng; et al. (Journal of Hazardous Materials, 2025)

Identification and characterization of 16 tripartite motif-containing proteins from Takifugu obscurus - Li-Fan Cui; Rui Shen; Xiao-Rui Song; Yan Shi; Zhe Zhao; Ying Huang (Fish & Shellfish Immunology, 2025)

Programmable allosteric DNA nanomachine for ratiometric imaging of VEGF in tumor cells - Jia-Wei Liang; Yan-Mei Lei; Zhao-Peng Chen; Xue-Mei Zhou; Ya-Qin Chai; Ruo Yuan; Rui Du; Ying Zhuo (Chemical Engineering Journal, 2025)

Atomically dispersed iron & iron clusters synergistically accelerate electrocatalytic ammonia synthesis - Haoran Zhang; Yuelong Liu; Sanshuang Gao; Haijian Wang; Rui Bai; Yan Zhao; Yingtang Zhou; Guangzhi Hu; Xue Zhao (Chemical Engineering Journal, 2025)

Effective identification of debris-covered glaciers in Western China using multiple machine-learning algorithms - Rui He; Donghui Shangguan; Qiudong Zhao; Shiqiang Zhang; Zizhen Jin; Yan Qin; Yaping Chang (Science of The Total Environment, 2024)

Unveiling spatiotemporal distribution, partitioning, and transport mechanisms of tire additives and their transformation products in a highly urbanized estuarine region - Hai-Yan Zhang; Yue-Hong Liu; Li-Ni Wei; Rui-Qi Zhu; Jian-Liang Zhao; Shan Liu; Xiang-Rong Xu; Guang-Guo Ying (Science of The Total Environment, 2024)

β-Caryophyllene oxide inhibits lysine acetylation of histones in Fusarium proliferatum to block ribosomal biosynthesis and function - Hong-Xin Liao; Jing Yang; Jin-Rui Wen; Hong-Yan Nie; Jun Zhao; Fu-Rong Xu; Xiao-Yun Liu; Xian Dong (Pesticide Biochemistry and Physiology, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Green fabrication of modified lignin/zeolite/chitosan-based composite membranes for preservation of perishable foods - Zhan-Chao Li; Meng-Yao Su; Xiao-Yu Yuan; Hai-Qing Lv; Rui Feng; Li-Jie Wu; Xiao-Ping Gao; Yan-Xia An; Zhan-Wei Li; Miao-Yun Li; Gai-Ming Zhao; Xiao-Peng Wang (Food Chemistry, 2024)

The inoculation of Bacillus paralicheniformis and Streptomyces thermoviolaceus enhances the lignocellulose degradation and microbial communities during spent mushroom substrate composting - Jiao Zhang; Ya-Jie Zou; Shun-Li Wang; Wei-Wei Zhang; Qing-Jun Chen; Qiu-Ying Wang; Ti-Kun Guan; Jia-Yan Zhang; Min-Rui Zhao; Guo-Qing Zhang (Environmental Research, 2024)

Crystal and micro-nano structure bidirectional regulation of iron oxalate for high-lithium storage and ultralong-cycling life via ultrasound assistance - Qing Zhao; Keyu Zhang; Geng Gao; Bo Jin; Guangping Zi; Rui Yan; Binbin Li; Bin Yang; Yaochun Yao (Chemical Engineering Journal, 2024)

Sirtuin 7 ameliorates cuproptosis, myocardial remodeling and heart dysfunction in hypertension through the modulation of YAP/ATP7A signaling - Yu-Fei Chen; Rui-Qiang Qi; Jia-Wei Song; Si-Yuan Wang; Zhao-Jie Dong; Yi-Hang Chen; Ying Liu; Xin-Yu Zhou; Jing Li; Xiao-Yan Liu; Jiu-Chang Zhong (Apoptosis, 2024)

Myosuppressin signaling deficiency affects ovarian development via repression of 20-hydroxyecdysone biosynthesis in Grapholita molesta - Jie Cheng; Jing-Kai Liu; Tian-Li Wang; Wei Wei; Hui-Ming Xiang; Xian-Wei Li; Rui-Yan Ma; Zhi-Guo Zhao (Pesticide Biochemistry and Physiology, 2024)

Structurally programmed bioderived polyimide for foldable humidity sensors with ultrafast response and recovery times - Caihong Gong; Huilong Liu; Shaoji Wu; Zhao Liu; Sutong Zheng; Yanhuang Tang; Zhiming Qiu; Rui Zhang; Yurong Yan (Chemical Engineering Journal, 2024)

External ligand-free nickel-catalyzed synthesis of polypyrazines towards stable, high-capacity and low-potential sodium ion storage - Zhihui Wang; Rui Li; Guoqing Zhao; Xiaorong Yan; Xinyu Wang; HaiPing Yu; Yuxin Hao; Yujie Dai; Huige Ma; Mengxiao Li; Hongwei Li; Mingsheng Yang; et al. (Chemical Engineering Journal, 2024)

Unveiling the evolutionary dynamics of microRNA-targeted plant laccase genes - Rui-Rui He; Meng-Qi Lei; Yan-Zhao Feng; Jiao Xue; Yu-Chan Zhang; Yue-Qin Chen; Yang Yu (Science China Life Sciences, 2024)

Disruption of a glycosyl transferase family 17 protein alters cadmium accumulation and resistance in rice (Oryza sativa) - Chun Yan Tu; Rui Guo; Chang Zhao Chen; Yong Qiang Gao; Lu Zheng; Qiang Zhang; Ren Fang Shen; Xiao Fang Zhu (Plant and Soil, 2024)

Response of soil quality degradation to cultivation and soil erosion: A case study in a Mollisol region of Northeast China - Rui Ma; Zhiyuan Tian; Yan Zhao; Yihang Wu; Yin Liang (Soil and Tillage Research, 2024)

Complete genome sequence of the 4-hydroxybenzoate-degrading bacterium Gymnodinialimonas sp. 57CJ19, a potential novel species from intertidal sediments - Dong-Hui Li; Ning Zheng; Zhen-Hai Liu; Xiao-Rui Dong; Chen Zhao; Shi-Gan Yan; Bin-Bin Xie (Marine Genomics, 2024)

Migration mechanism of atrazine in the simulated lake icing process at different freezing temperatures based on density function theory - Yan Zhang; Hao Lin; Aixin Yu; Xiaozhuang Wang; Yucan Liu; Tongshuai Liu; Chen Zhao; Rui Mei (Journal of Environmental Sciences, 2024)

Portulaca oleracea L. polysaccharide ameliorates ulcerative colitis by regulating the immune system and gut microbiota - Yang Yang; Xiechen Zhou; Guiyan Jia; Hui Zhao; Yan Li; Junyang Cao; Zijian Guan; Rui Zhao (Food Bioscience, 2024)

Effects of Spraying Allantoin at Different Stages on Inorganic Nitrogen Assimilation, Endogenous Hormones, Yield, and Quality of Sugar Beet in Saline-Alkali Land - Xin-Rui Yu; Jia-Nan Zhao; Yan-Long Zhuang; Ling-Hua Zhao; Chao Wang; Xiao-Fei Yang; Yu-Bo Wang; Cai-Feng Li (Sugar Tech, 2024)

Optimizing waste leachate treatment for environmental and economic sustainability: Insights from a bottom-up study of over 300 cities - Qian-long Han; Hai-long Zhao; Guo-xia Wei; Han-qiao Liu; Yu-wen Zhu; Tong Li; Yan-fei Lin; Xin-rui Su (Sustainable Production and Consumption, 2024)

A bi-layer task decision-making approach for USV clusters with multi-constrained task points - Xiaoming Zhao; Rui Song; Yangmin Xie; Zihao Wang; Yan Peng (Ocean Engineering, 2024)

Constructing interfacial chemical interaction of dual-carbon protected cobalt diselenide anode for sodium storage - Xiaoying Liu; Dongdong Xue; Rui Ren; Ting Ou; Tao Sun; Yuchen Han; Fan Jin; Yannan Li; Yan Zhao; Jiangwei Zhang (Chemical Engineering Journal, 2024)

Progressive Freezing-Melting Method for Removal Boron from Simulated Seawater - Yihong Zou; Yan Zhang; Chen Zhao; Rui Mei; Lin Lin; Chunbo Liu; Yucan Liu; Yepeng Tian; Futian Chen (Water, Air, & Soil Pollution, 2024)

Mutations in wheat TaAPA2 gene result in pleiotropic effects on plant architecture - Shengsheng Bai; Guiping Wang; Rui Song; Yanna Liu; Lei Hua; Jinwei Yang; Lijun Zhang; Shams ur Rehman; Xiaohua Hao; Lifeng Hou; Chaozhong Zhang; Hongna Li; et al. (Science China Life Sciences, 2024)

Molecular characterization of fad6 gene and its transcriptional changes in response to different initial diets and nutritional status in yellow catfish (Pelteobagrus fulvidraco) - Bo Zhou; Xiu-Ying Wei; Zheng-Yong Wen; Bin Wang; Yu-Ying Zhao; Wan-Hong Zeng; Yu He; Panita Prathomya; Yun-Yun Lv; Yan-Ping Li; Jun Wang; Rui Li; et al. (Frontiers in Marine Science, 2024)
Fatty acid desaturases (FADs) are rate-limiting enzymes for the biosynthesis of highly unsaturated fatty acids (HUFAs). As a new member of the FAD family, Fad6 and its roles remain unclear in various teleost fishes. In this study, we identified a fad6 gene from yellow catfish (yc fad6 ) and determined its spatiotemporal expression patterns and responses to different initial diets and nutritional status in yellow catfish. Our results showed that the open reading frame (ORF) of yc fad6 was 1,080 bp in length, encoding a protein of 359 amino acids. Multiple protein sequences alignment proved that fad6 is highly conserved among diverse vertebrates. Meanwhile, phylogenetic analysis revealed that Southern catfish and yellow catfish were clustered into one branch, supporting evolutionary consistence between the fad6 gene and fish morphology. Moreover, comparisons of genomic synteny and gene structure revealed functional and evolutionary conservation of the fad6 gene in various teleost fishes. Tissue distribution analysis by quantitative RT-PCR demonstrated that the yc fad6 gene was extensively expressed in examined tissues, with higher transcription levels in the heart and liver. Meanwhile, yc fad6 gene was widely expressed in various developmental stages, indicating Fad6 may play important roles in HUFA biosynthesis at early developmental stages in yellow catfish. Functional experiments verified that the transcription of yc fad6 decreased significantly with the extension of feeding time (with egg yolk or Artemia nauplii ) at the early developmental stages, indicating that a diet rich in HUFA can remarkably inhibit the transcription of yc fad6 in yellow catfish. In addition, yc fad6 transcription was significantly reduced after a short-term (24-h) or long-term food deprivation (1-week) and then continued to decrease during refeeding, suggesting that nutritional states can affect the transcription of yc fad6 , which further regulates the metabolism of HUFAs. Anyway, these fundamental findings provide basic references for further investigating evolutionary and physiological functions of the fad6 gene in yellow catfish as well as in other teleost fishes.

Karst carbon sink mechanism and its contribution to carbon neutralization under land- use management - Min Zhao; Dong Li; Zaihua Liu; Qian Bao; Fan Xia; Hao Yan; Bo Chen; Yundi Hu; Guanxia Cai; Rui Lang; Hang Li; Liangxing Shi; et al. (Science of The Total Environment, 2024)

Feasibility of nanofiltration process for efficient separation of gallic acid from the extract of black tea in aqueous solution - Yiwei Dong; Rui Zhao; Chunyan Xu; Jinxin Liu; Zhiguo Dong; Ziqi Chen; Jinfeng He; Chuanrun Li; Haiyang Yan; Li Sun (Journal of Water Process Engineering, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

Active prelithiation strategies for advanced lithium storage systems: A perspective from electrochemical mechanism to structural design and application - Bo Jin; Keyu Zhang; Geng Gao; Qing Zhao; Xinyu Jiang; Dingfang Cui; Keqi Chen; Xiang Lin; Liuliu Liu; Rui Yan; Bin Yang; Yaochun Yao (Chemical Engineering Journal, 2024)

Isolation, identification and transcriptome analysis of triadimefon-degrading strain Enterobacter hormaechei TY18 - Yan Wang; Qi Guan; Wenhui Jiao; Jiangbo Li; Rui Zhao; Xiqian Zhang; Weixin Fan; Chunwei Wang (Biodegradation, 2024)

Populus euphratica R2R3-MYB transcription factor RAX2 binds ANN1 promoter to increase cadmium enrichment in Arabidopsis - Caixia Yan; Bing Feng; Ziyan Zhao; Ying Zhang; Kexin Yin; Yi Liu; Xiaomeng Zhang; Jian Liu; Jing Li; Rui Zhao; Nan Zhao; Xiaoyang Zhou; et al. (Plant Science, 2024)

Serpentinite geochemistry documents the earliest dehydration and decarbonation of the subducting slab beneath the Mariana forearc - Rui-Peng Zhao; Hong-Yan Li; Jeffrey G. Ryan; Raymond M. Johnston; Owen Jensen; Yi-Gang Xu (Earth and Planetary Science Letters, 2024)

N-doped carbon dots/g-C3N4 photoexcitation simultaneously enhanced the microbial degradation of nitrate and oxytetracycline in a low C/N ratio aquaculture wastewater - Pin Peng; Lixiang Chen.; Xinyu Yan; Rui Bai; Bob Adyari; Xudong Zhou; Feng Zhao (Chemical Engineering Journal, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

Geochemistry of metabasite in Mariana forearc serpentinite mudflows documents interactions between serpentinizing fluid and subducted seamount basalts - Rui-Peng Zhao; Hong-Yan Li; Jeffrey G. Ryan; Xun Wei; Sheng-Xiong Yang; Yi-Gang Xu (Chemical Geology, 2024)

Two new sesterterpenoids from Atractylodes japonica Koidz. ex Kitam - Yuan-Yuan Zhou; Zhao Sun; Yan Liu; Zhen-Xing Fang; Hui-Rui Gao; Ning-Yu Liu; Xiao-Juan Zhang; Bing-You Yang; Hai-Xue Kuang (Journal of Natural Medicines, 2024)

Two new cytochalasins from the endophytic fungus Xylaria sp. GDGJ-77B - Zhao-Long Xu; Ben-Chao Li; Li-Li Huang; Liu-Xia Lv; Yan Luo; Wei-Feng Xu; Rui-Yun Yang (Natural Product Research, 2024)

A novel aldo-keto reductase gene, OsAKR1, from rice confers higher tolerance to cadmium stress in rice by an in vivo reactive aldehyde detoxification - Rui Guo; Qiang Zhang; Chang Zhao Chen; Jie Ya Sun; Chun Yan Tu; Meng Xing He; Ren Fang Shen; Jiu Huang; Xiao Fang Zhu (Journal of Hazardous Materials, 2024)

Synergistic enhancement of phase change materials through three-dimensional porous layered covalent triazine framework/expanded graphite composites for solar energy storage and beyond - Long Geng; Jiapeng Wang; Xulong Yang; Jiaping Jiang; Rui Li; Yabo Yan; Jiateng Zhao; Changhui Liu (Chemical Engineering Journal, 2024)

Growth differentiation factor 9 regulates the expression of estrogen receptors via Smad2/3 signaling in goat cumulus cells - Yaju Tang; Sihai Lu; Juncai Wei; Rui Xu; Hui Zhang; Qiang Wei; Bin Han; Yan Gao; Xiaoe Zhao; Sha Peng; Menghao Pan; Baohua Ma (Theriogenology, 2024)

Carbazomycins I and J, two novel carbazole alkaloids isolated from Saccharopolyspora phattalungensis - Wen Wang; Er Juan Zhao; Ting Peng; Zhang Yuan Yan; Zhi Kai Guo; Rui Hua Jiao (Phytochemistry Letters, 2024)

Hollow α-Bi2O3/TiO2 nanotube arrays hierarchical heterojunction with strong interface interaction for efficient photocatalytic ciprofloxacin degradation - Bingrui Ma; Yuxin Zha; Rui Xu; Jincheng Li; Yajing Guo; Jie Liu; Songxue Wang; Boyin Yan; Yunlong Lan; Baoxiu Zhao; Haijiao Xie (Journal of Water Process Engineering, 2024)

Constructing of Fe-Cu bimetallic MOFs derived electro-Fenton cathode for efficient norfloxacin removal - Yixin Du; Zhenpeng Li; Rui Feng; Qing Liu; Yanming Yang; Meng Sun; Yanxia Zhao; Tao Yan; Liangguo Yan (Journal of Environmental Chemical Engineering, 2024)

Sulfate-functionalized Fe-based MOF for removal of Pb(Ⅱ) and NO3- in industrial wastewater - Rui-Dong Wang; Wen-Qian Zhang; Hong-Bo Lv; Yan-Ting Chen; Lei Wang; Si-Han Zhou; Lin Du; Qi-Hua Zhao (Journal of Environmental Chemical Engineering, 2024)

A polypyrrole-dopamine/poly(vinyl alcohol) anisotropic hydrogel for strain sensor and bioelectrodes - Shuang Chen; Bingyan Guo; Jiajun Yu; Zhuojun Yan; Rui Liu; Chaojie Yu; Zhongming Zhao; Hong Zhang; Fanglian Yao; Junjie Li (Chemical Engineering Journal, 2024)

Two-dimensional peak-valley alternating self-supporting electrode accelerating nitrate electrocatalytic reduction: Ammonia synthesis and wastewater treatment - Yuelong Liu; Haoran Zhang; Rui Bai; Haijian Wang; Yan Zhao; Yingtang Zhou; Xue Zhao (Chemical Engineering Journal, 2024)

The pH adjustment of Vitis amurensis dry red wine revealed the evolution of organic acids, volatomics, and sensory quality during winemaking - Meng-Bo Tian; Rui-Qi Hu; Zhao-Long Liu; Ning Shi; Hao-Cheng Lu; Chang-Qing Duan; Jun Wang; Yan-Feng Sun; Qing-Sen Kong; Fei He (Food Chemistry, 2024)

Low-carbon production performance of agricultural green technological innovation: From multiple innovation subject perspective - Rui Shi; Liuyang Yao; Minjuan Zhao; Zheming Yan (Environmental Impact Assessment Review, 2024)

Improving categorical and continuous accuracy of precipitation forecasts by integrating Empirical Quantile Mapping and Bernoulli-Gamma-Gaussian distribution - Lingjie Li; Zhaode Yun; Yong Liu; Yintang Wang; Wenpeng Zhao; Yan Kang; Rui Gao (Atmospheric Research, 2024)

Ubiquitination-dependent protein homeostasis is critical for the thermotolerance of the economically valuable seaweed Pyropia haitanensis - Rui Zhao; Jian Wen; Kai Xu; Yan Xu; Dehua Ji; Chaotian Xie; Wenlei Wang (Aquaculture, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Effect of simplified inoculum agent on performance and microbiome during cow manure-composting at industrial-scale - Weiwei Dong; Rui Zhou; Xudong Li; Hua Yan; Jinshui Zheng; Nan Peng; Shumiao Zhao (Bioresource Technology, 2024)

Boron removal in seawater desalination by progressive freezing-melting - Rui Mei; Tongguo Zhao; Yan Zhang; Hao Lin; Chen Zhao; Lin Lin; Yihong Zou; Yucan Liu (Environmental Science and Pollution Research, 2024)

Identification and characterization of an L-type lectin from obscure puffer Takifugu obscurus in response to bacterial infection - Fu-Hui Jiang; Ying Huang; Xin-Yue Yu; Li-Fan Cui; Yan Shi; Xiao-Rui Song; Zhe Zhao (Fish & Shellfish Immunology, 2024)

A high-resolution α-glucosidase inhibition profiling for targeted identification of natural antidiabetic products from Lycopodiella cernua (L.) Pic. Serm and their inhibitory mechanism study - Bing-Rui Liu; Xu-Liu Shi; Jian-Kun Yan; Rui Zhao (Natural Product Research, 2023)

Roxarsone biotransformation by a nitroreductase and an acetyltransferase in Pseudomonas chlororaphis, a bacterium isolated from soil - Jie-wen Ma; Gui-wen Liu; Jia-Yu Zhai; Ke-qian Zhao; Ya-qing Wu; Rui-lian Yu; Gong-ren Hu; Yu Yan (Chemosphere, 2023)

CD4 is an important host factor for Japanese encephalitis virus entry and replication in PK-15 cells - Qi Wang; Shuqing Yang; Ke Yang; Xinran Li; Yu Dai; Yi Zheng; Sanjie Cao; Qigui Yan; Xiaobo Huang; Yiping Wen; Qin Zhao; Senyan Du; et al. (Veterinary Microbiology, 2023)

The co-regulation of the gut microbiome and host genes might play essential roles in metformin gastrointestinal intolerance - Huixiang Zhang; Jiao Lai; Lihuan Zhang; Wei Zhang; Xun Liu; Qilin Gong; Hongxi Tian; Mingzhi Yang; Tao Yang; Rui Zhao; Dongqing Li; Hehua Huang; et al. (Toxicology and Applied Pharmacology, 2023)

Binding divergence of polystyrene nanoparticles with serum albumin caused by surface functionalization - Jing Lan; Yaoyao Wang; Haimei Li; Rui Guan; Zongshan Zhao; Yan Bao; Xianfa Du; Henner Hollert; Xingchen Zhao (Science of The Total Environment, 2023)

Protective and immunomodulatory effects of mesenchymal stem cells on multiorgan injury in male rats with heatstroke - Yuyan Liu; Yun Li; Zihui Deng; Yan Zhao; Rui Yuan; Mengmeng Yang; Lu Wang; Yuan Fang; Dengfeng Ding; Feihu Zhou; Hongjun Kang (Journal of Thermal Biology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

The role of climate-adaptive technological innovation in promoting agriculture carbon efficiency: impact and heterogeneity in economic development - Rui Shi; Liuyang Yao; Minjuan Zhao; Zheming Yan (Environmental Science and Pollution Research, 2023)

Different responses of precipitation patterns to the East Asian summer monsoon weakening: The 7.2 and 8.2 ka events - Liangkang Pan; Jingyao Zhao; Yan Yang; Kexin Wang; Carlos Pérez-Mejías; Jiahui Cui; Xiyu Dong; Rui Zhang; Hai Cheng (Quaternary Science Reviews, 2023)

Hydrophobic aggregation via partial Gal removal affects solution characteristics and fine structure of tamarind kernel polysaccharides - Rui Guo; Xianbao Sun; Yuxing Kou; Hong Song; Xujiao Li; Lihua Song; Taolei Zhao; Hui Zhang; Deshun Li; Yanfang Liu; Zibo Song; Jieli Wu; et al. (Food Hydrocolloids, 2023)

Epithelial lining inspired protective shield for prolonged endotracheal intubation - Baisong Zhao; Meng-Han Bai; Luxi Zhang; Qingning Wang; Yongying Pan; Yan-Pu Li; Rui Hong; Juxiang Gou; Dongjie Zhang; Yuwei Liu; Gan-Ji Zhong; Ka Li; et al. (Chemical Engineering Journal, 2023)

New insight into opposite oxidation behavior in acetone and propane catalytic oxidation over CoMn based spinel oxides - Cangpeng Shan; Yan Zhang; Qian Zhao; Jianbo Li; Yunchong Wang; Rui Han; Caixia Liu; Qingling Liu (Chemical Engineering Journal, 2023)

Transient, printable and recyclable gelatin hydrogels with enhanced mechanical sensing and electromagnetic shielding performance by incorporation of reduced graphene oxide - Rui Yin; Chen Zhang; Youyou Chen; Yu Wang; Qiang Feng; Yaming Liu; Minghan Yu; Yunhuan Yuan; Cheng-Yan Xu; Feihua Liu; Weiwei Zhao (Chemical Engineering Journal, 2023)

Magmatic fluids responsible for lode gold mineralization in the giant Linglong deposit at Jiaodong, North China Craton: Constraints from LiO isotopes - Shao-Rui Zhao; Zhan-Ke Li; Zu-Wei Lin; Jian-Feng Gao; Hua-Shan Sun; Martin Yan Hei Li; Xin-Fu Zhao (Chemical Geology, 2023)

Microplastics affect soil bacterial community assembly more by their shapes rather than the concentrations - Peng-Yang Wang; Ze-Ying Zhao; Xiao-Bin Xiong; Ning Wang; Rui Zhou; Zhi-Ming Zhang; Fan Ding; Meng Hao; Song Wang; Yue Ma; Aimee Grace Uzamurera; Kai-Wen Xiao; et al. (Water Research, 2023)

IFN-γ promotes PANoptosis in Pasteurella multocida toxin-induced pneumonia in mice - Hang Xiao; Qin Zhao; Jianlin Yuan; Wei Liang; Rui Wu; Yiping Wen; Senyan Du; Yiping Wang; Shan Zhao; Yifei Lang; Qigui Yan; Xiaobo Huang; et al. (Veterinary Microbiology, 2023)

Association between urinary neonicotinoid insecticide levels and dyslipidemia risk: A cross-sectional study in Chinese community-dwelling elderly - Jian Sun; Pei He; Rui Wang; Zhong-Yuan Zhang; Yu-Qing Dai; Xiao-Yu Li; Si-Yu Duan; Cai-Ping Liu; Hao Hu; Guang-Jun Wang; Yan-Ping Zhang; Fei Xu; et al. (Journal of Hazardous Materials, 2023)

The active synergetic microbiota with Aspergillus as the core dominates the metabolic network of ester synthesis in medium-high temperature Daqu - Yan Wang; Shikai Quan; Yajiao Zhao; Yu Xia; Rui Zhang; Maofang Ran; Zhengyun Wu; Wenxue Zhang (Food Microbiology, 2023)

Effects of Fe and cost-effective media composition on arsenopyrite bioleaching by Sulfobacillus thermosulfidooxidans - Hong-Rui Chen; Duo-Rui Zhang; Xiao-Juan Zhao; Qian Li; Yu-Ting Liang; Eva Pakostova; Yan Zhang; Yong-Bin Yang (Chemical Engineering Journal, 2023)

Polar-facing slopes showed stronger greening trend than equatorial-facing slopes in Tibetan plateau grasslands - Gaofei Yin; Xinyu Yan; Dujuan Ma; Jiangliu Xie; Rui Chen; Huiqin Pan; Wei Zhao; Changting Wang; Aleixandre Verger; Adrià Descals; Iolanda Filella; Josep Peñuelas (Agricultural and Forest Meteorology, 2023)

Megastigmane sesquiterpenoids from Saussurea medusa and their anti-inflammatory activities - Jing-Ya Cao; Qi Dong; Zhi-Yao Wang; Ye Zhao; Yu Ren; Li-Juan Mei; Yan-duo Tao; Rui-Tao Yu (Natural Product Research, 2023)

Farmers’ participation into the recovery of waste agricultural plastic film: An application of the Theory of Planned Behavior - Ze-Ying Zhao; Wen-Bo Li; Peng-Yang Wang; Hong-Yan Tao; Rui Zhou; Jin-Ying Cui; Jian Zhang; Tao Tian; Xu-Zhe Zhao; Yi-Bo Wang; You-Cai Xiong (Waste Management, 2023)

Integrating data dependent and data independent non-target screening methods for monitoring emerging contaminants in the Pearl River of Guangdong Province, China - Rui Wang; Yanan Yan; He Liu; Yanxi Li; Meng Jin; Yuqing Li; RiZhu Tao; Qianghua Chen; Xuguang Wang; Bo Zhao; Danping Xie (Science of The Total Environment, 2023)

Investigating the electrochemical performance of MnO2 polymorphs as cathode materials for aqueous proton batteries - Yujie Dai; Jianze Zhang; Xiaorong Yan; Guoqing Zhao; Mingsheng Yang; Jiakui Xiong; Rui Li; Naihua Miao; Haiping Yu; Mingjun Hu; Jingru Liu; Jun Yang (Chemical Engineering Journal, 2023)

Unraveling the role of unpaired 3d electrons in e orbital of CoO: Driving π feedback of N2 for efficient ammonia electrosynthesis - Yuanyuan Xiong; Liang Zhao; Rui Zhao; Xiaoxuan Wang; Xinyue Chi; Kaixin Zhang; Zhenzhen Fu; Shuyuan Li; Jiaou Wang; Kaiqi Nie; Zhiyu Yang; Yi-Ming Yan (Chemical Engineering Journal, 2023)

Moringa oleifera Lam. leaves as new raw food material: A review of its nutritional composition, functional properties, and comprehensive application - Min Yang; Liang Tao; Xin-Rui Kang; Zi-Lin Wang; Ling-Yan Su; Ling-Fei Li; Fan Gu; Cun-Chao Zhao; Jun Sheng; Yang Tian (Trends in Food Science & Technology, 2023)

Dynamic probabilistic risk assessment of emergency response for intelligent coal mining face system, case study: Gas overrun scenario - Yan Zhang; Yu-Hao Wang; Xu Zhao; Rui-Peng Tong (Resources Policy, 2023)

Influence of calcination temperature on the evolution of α-MoO3 nanosheets catalyst for aqueous phase reforming of biogas slurry - Jian Wang; Yuxuan Chen; Weigao Zhao; Rui Liang; Beibei Yan; Junyu Tao; Hong Su; Guanyi Chen (Fuel, 2023)

Chemical constituents from the pericarps of Zanthoxylum bungeanum Maxim. and their chemotaxonomic significance - Bang-Yin Tan; Cai-Feng Ding; Rui-Rong Guo; Jing-Zhi Zhao; Di-Wei Ma; Kun Fan; Lan-Chun Zhang; Rong-Ping Zhang; Wei-Yan Hu; Hao-Fei Yu (Biochemical Systematics and Ecology, 2023)

Thickness effects of polyethylene and biodegradable film residuals on soil properties and dryland maize productivity - Aimee Grace Uzamurera; Ze-Ying Zhao; Peng-Yang Wang; Yong-Xian Wei; Fei Mo; Rui Zhou; Wen-Li Wang; Fazal Ullah; Aziz Khan; Xiao-Bin Xiong; Meng-Ying Li; Kiprotich Wesly; et al. (Chemosphere, 2023)

Atmospheric ammonia in China: Long-term spatiotemporal variation, urban-rural gradient, and influencing factors - Jinyan Dong; Baojie Li; Yan Li; Rui Zhou; Cong Gan; Yongqi Zhao; Rui Liu; Yating Yang; Teng Wang; Hong Liao (Science of The Total Environment, 2023)

Combined effects of NaOH, NaCl, and heat on the characteristics of ovalbumin gel and the exploration of the mechanism of transparent gel formation - Hui Xue; Tianfeng Han; Guowen Zhang; Xiaobo Hu; Ruiling Li; Huilan Liu; Rui Li; Yonggang Tu; Yan Zhao (Food Hydrocolloids, 2023)

CRISPR-Cas12a powered multifunctional DNA nanodumbbell lock biosensor for multiple molecular detection - Yuqing Zhu; Xiaohe Zheng; Rui Zhu; Hongrui Zhao; Hongli Zhai; Feiyang Qian; Tenghua Zhang; Zihui Xie; Silan Liu; Bowen Jiang; Yan Sheng; Jiaming Hu (Chemical Engineering Journal, 2023)

Short-term effects of individual exposure to PM2.5 on hospital admissions for myocardial infarction and stroke: a population-based case-crossover study in Guangzhou, China - Jie-Qi Jin; Guo-Zhen Lin; Shuang-Ying Wu; Mu-Rui Zheng; Hui Liu; Xiang-Yi Liu; Min-Qian Yan; Zhao-Yue Chen; Chun-Quan Ou (Environmental Science and Pollution Research, 2023)

Experimental study on low-damage performance of Sliding Hinge Joint - Junrong Liu; Rui Zhang; Zhenduo Yan; Jiang-Yue Xie; Kim Eng Chouery; Liang-Jiu Jia; Ping Xiang; Xianzhong Zhao; Shahab Ramhormozian; Rajesh P. Dhakal; G. Charles Clifton; Gregory A. MacRae (Soil Dynamics and Earthquake Engineering, 2023)

Composition, metabolism and postharvest function and regulation of fruit cuticle: A review - Gang-Shuai Liu; Hong-Li Li; Zhen-Zhen Peng; Rui-Ling Liu; Yan-Chao Han; Yun-Xiang Wang; Xiao-Dan Zhao; Da-Qi Fu (Food Chemistry, 2023)

Can shallow-incorporated organic mulching replace plastic film mulching for irrigated maize production systems in arid environments? - Ze-Ying Zhao; Peng-Yang Wang; Xiao-Bin Xiong; Rui Zhou; Ying Zhu; Yi-Bo Wang; Ning Wang; Kiprotich Wesly; Wei Xue; Jing Cao; Jin-Lin Zhang; Hong-Yan Tao; et al. (Field Crops Research, 2023)

Simultaneously mapping loci related to two plant architecture traits by phenotypic recombination BSA/BSR in peanut (Arachis hypogaea L.) - Xiaona Yu; Yaoyao Li; Xinyuan Cui; Xianheng Wang; Jihua Li; Rui Guo; Fanzhuang Yan; Shaojing Zhang; Ruihua Zhao; Danlei Song; Tong Si; Xiaoxia Zou; et al. (Theoretical and Applied Genetics, 2023)

Experimental study on flow and heat transfer of supercritical carbon dioxide in zigzag channels with bending angle 30° for advanced nuclear systems - Sheng-hui Liu; Rui-long Liu; Yan-ping Huang; Xiao-liang Zhu; Liu Yang; Jia Tang; Bin Han; Tian-yang Xing; Xue-bin Zhao (Annals of Nuclear Energy, 2023)

Acrylamide in food: Occurrence, metabolism, molecular toxicity mechanism and detoxification by phytochemicals - Fangfang Yan; Li Wang; Li Zhao; Chengming Wang; Qun Lu; Rui Liu (Food and Chemical Toxicology, 2023)

Manipulating electron redistribution of active sites by in situ engineering B-S-V bond in VS2 catalyst for stable nitrogen fixation - Xinyue Chi; Rui Zhao; Xiaoxuan Wang; Yuanyuan Xiong; Kaixin Zhang; Zhenzhen Fu; Yebo Yao; Shuyuan Li; Zhi-Yu Yang; Yi-Ming Yan (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Pegmatite magmatic evolution and rare metal mineralization of the Dahongliutan pegmatite field, Western Kunlun Orogen: Constraints from the B isotopic composition and mineral-chemistry - Rui Cao; Yongbao Gao; Bin Chen; Leon Bagas; Shengchao Yan; Chao Huang; Hui Zhao (International Geology Review, 2023)

miR-503 targets MafK to inhibit subcutaneous preadipocyte adipogenesis causing a decrease of backfat thickness in Guanzhong Black pigs - Rui Cai; Mingkun Chao; Tiantian Zhao; Rui Li; Ziyi Zhang; Wenyong Yan; Weijun Pang (Meat Science, 2023)

Thickness-dependent release of microplastics and phthalic acid esters from polythene and biodegradable residual films in agricultural soils and its related productivity effects - Aimee Grace Uzamurera; Peng-Yang Wang; Ze-Ying Zhao; Xiu-Ping Tao; Rui Zhou; Wen-Ying Wang; Xiao-Bin Xiong; Song Wang; Kiprotich Wesly; Hong-Yan Tao; You-Cai Xiong (Journal of Hazardous Materials, 2023)

Peroxymonosulfate activation by Cu2O@CuO nanowires array-based electroactive filter for efficient ofloxacin removal - Rongshuai Wang; Haoqi Wang; Chongying Zhong; Qing Liu; Rui Feng; Yanxia Zhao; Meng Sun; Liangguo Yan; Tao Yan (Journal of Environmental Chemical Engineering, 2023)

Slab dehydration and magmatism in the Kurile arc as a function of depth: An investigation based on B-Sr-Nd-Hf isotopes - Hong-Yan Li; Chao Xie; Jeffrey G. Ryan; Chuan-Mao Yang; Rui-Peng Zhao; Chao Zhang; Yi-Gang Xu (Chemical Geology, 2023)

rTFPI Protects Cardiomyocytes from Hypoxia/Reoxygenation Injury through Inhibiting Autophagy and the Class III PI3K/Beclin-1 Pathway - Runan Yan; Wei Gao; Wenjia Chen; Yue Liu; Li Shen; Yue Dai; Rui Xu; Qing Chang; Yu Fu; Yong Zhao (Cell Biochemistry and Biophysics, 2023)

Probabilistic prediction of ground-motion intensity for regions lacking strong ground-motion records - Yan-Gang Zhao; Rui Zhang; Haizhong Zhang (Soil Dynamics and Earthquake Engineering, 2023)

In situ degradation of low-density polyethylene film in irrigation maize field: Thickness-dependent effect - Xiao-Bin Xiong; Ze-Ying Zhao; Peng-Yang Wang; Rui Zhou; Jing Cao; Jing Wang; Kiprotich Wesly; Wen-Li Wang; Ning Wang; Meng Hao; Yi-Bo Wang; Hong-Yan Tao; et al. (Science of The Total Environment, 2023)

Sodium hydrosulfide alleviates aluminum toxicity in Brassica napus through maintaining H2S, ROS homeostasis and enhancing aluminum exclusion - Yan Yu; Jia Dong; Rui Li; Xue Zhao; Zonghe Zhu; Fugui Zhang; Kejin Zhou; Xianyong Lin (Science of The Total Environment, 2023)

How seasonality affects the environmental performance of fresh appetite: Insights from cherry consumption in China - Xin Xiong; Junyi Shen; Yan Hao; Lixiao Zhang; Rui Zhao; Shoujuan Tang; Xinqing Li; Zhimin Shi (Journal of Environmental Management, 2023)

Molecular characterization and immune functions of lipasin in Nile tilapia (Oreochromis niloticus): Involvement in the regulation of tumor necrosis factor-α secretion - Rui Dong; Zixi Wang; Qianqian Zhao; Yisha Yan; Quan Jiang (Fish & Shellfish Immunology, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Selenite Ameliorates Cadmium-induced Cytotoxicity Through Downregulation of ROS Levels and Upregulation of Selenoprotein Thioredoxin Reductase 1 in SH-SY5Y Cells - Hecheng Wang; Shibo Sun; Yan Ren; Rui Yang; Jianli Guo; Yu Zong; Qiuxian Zhang; Jing Zhao; Wei Zhang; Weiping Xu; Shui Guan; Jianqiang Xu (Biological Trace Element Research, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Pricing method and empirical study of China’s sea area resources assets - Tao Wang; Lu Yang; Rui Zhao; Stephen Hynes; Yue Yin; Cunji Liu; Yan Zheng; Lijing Deng (Journal of Coastal Conservation, 2022)

Vitamin D3 affects browning of white adipocytes by regulating autophagy via PI3K/Akt/mTOR/p53 signaling in vitro and in vivo - Yan Zhao; Rui Qin (Apoptosis, 2022)

ACC deaminase-encoding Pseudomonas putida arrests seed germination: an alternative strategy for grass and weed control - Di Zhou; Jia-Ling Zhao; Rui Wang; Hai-Lin Wang; Daniela D. Herrera-Balandrano; Tang-Min Chen; Xiao-Feng Lu; Xu-Chu Duan; Mahdi Shahriar; Xin-Chi Shi; Pedro Laborda; Su-Yan Wang (Plant and Soil, 2022)

Integrated mosquito management in rice field in China - Tong-Yan Zhao; Rui-De Xue (Wetlands Ecology and Management, 2022)
Rice cultivation is important in China with over 29.33 million hm 2 of rice fields, producing 28.9% of rice yields worldwide. Rice fields are mass breeding sites for mosquitoes with approximately 40 mosquito species found breeding amongst them. Anopheles sinensis , Anopheles lesteri , and Culex tritaeniorhynchus are the three main species that are found breeding in rice fields. An. sinensis and An. lesteri are important vectors of malaria in flat areas of China, and Cx. tritaeniorhynchus is a main vector of Japanese B encephalitis. This review provides the principles of mosquito control used to target the species of mosquitoes breeding in rice fields, as well as some main approaches that have been tested and implemented for mosquito control in the past 70 years. The irrigation management of rice fields is included, such as intermittent irrigation, wet irrigation, controlled irrigation, and rotation of rice fields and dry fields. Biocontrol measures and agents, including rice-fish coculture, Azolla , Bacillus thuringiensis israelensis ( Bti ), and Bacillus sphaericus , for mosquito control are discussed. These control methods benefit the prevention and control of mosquito-borne disease, especially malaria elimination in China.

A Label-Free Colorimetric Aptasensor Containing DNA Triplex Molecular Switch and AuNP Nanozyme for Highly Sensitive Detection of Saxitoxin - Xiaoyan Qi; Ling Li; Xiaochen Yan; Yinglin Zhao; Lele Wang; Rui Ma; Sai Wang; Xiangzhao Mao (Journal of Ocean University of China, 2022)

Direct Radiative Effects of Dust Aerosols over Northwest China Revealed by Satellite-Derived Aerosol Three-Dimensional Distribution - Rui Jia; Yuzhi Liu; Yan Li; Jun Li; Xiaolin Hu; Ronglu Gao; Yunfei Tian; Yanling Sun; Nannan Mu; Minfen Zhao (Journal of Meteorological Research, 2022)

Roseicella aquatilis sp. nov., isolated from freshwater lake - Dan-Dan Zhang; Ya-Nan Zhao; Rui-Han He; Yu-Qi Yan; Zong-Jun Du (Archives of Microbiology, 2022)

Toxic encephalopathy induced by radix Sophorae tonkinensis - Xue-Lin Li; Hao-Tian Zhao; Jinming Han; Zhong-Rui Yan; Hai-Yang Wang (Acta Neurologica Belgica, 2022)

Rare soil species impact the rhizosphere bacterial communities and cadmium uptake by Lolium multiflorum Lam. - Chenxin Gao; Yan Zhu; Xian Xiao; Rui Liu; Xuesong Zhu; Yuan Zhao (Plant and Soil, 2022)

Development of a Label-Free Colorimetric Aptasensor with Rationally Utilized Aptamer for Rapid Detection of Okadaic Acid - Xiaochen Yan; Xiaoyan Qi; Yinglin Zhao; Ling Li; Rui Ma; Lele Wang; Sai Wang; Xiangzhao Mao (Journal of Ocean University of China, 2022)

Two new sesquiterpenes from the rhizomes of Atractylodes macrocephala and their biological activities - Yi-Nan Zhao; Gai Gao; Jin-Lian Ma; Rui-Zhu Xu; Tao Guo; Li-Min Wu; Xin-Guang Liu; Zhi-Shen Xie; Jiang-Yan Xu; Zhen-Qiang Zhang; Pan Wang (Natural Product Research, 2022)

Evaluation of the Crack Propagation Capacity of Hard Rock Based on Stress-Induced Deformation Anisotropy and the Propagation Angle of Volumetric Strain - Qiang Han; Xia-Ting Feng; Chengxiang Yang; Rui Kong; Jun Zhao; Yan Zhang (Rock Mechanics and Rock Engineering, 2021)

Change detection in remote sensing images based on manifold regularized joint non-negative matrix factorization - Weidong Yan; Xinxin Liu; Jinhuan Wen; Jinfeng Hong; Sa Zhang; Rui Zhao (Earth Science Informatics, 2021)

Comparative transcriptome analysis reveals that deletion of CheY influences gene expressions of ABC transports and metabolism in Haemophilus parasuis - Lvqin He; Xuefeng Yan; Ke Dai; Xintian Wen; Sanjie Cao; Xiaobo Huang; Rui Wu; Qin Zhao; Yong Huang; Qigui Yan; Xiaoping Ma; Xinfeng Han; et al. (Functional & Integrative Genomics, 2021)

Echinicola salinicaeni sp. nov., a novel bacterium isolated from saltern mud - Han Zhao; Chun-Yi Song; Rui Yin; Yan-Jun Yi; Shuai-Ting Yun; Ying-Xiu Li; Yan-Xia Zhou (Antonie van Leeuwenhoek, 2021)

Numerical Investigation of the Characteristics of Erosion in a Centrifugal Pump for Transporting Dilute Particle-Laden Flows - Rui-Jie Zhao; You-Long Zhao; De-Sheng Zhang; Yan Li; Lin-Lin Geng (Journal of Marine Science and Engineering, 2021)
Erosion in centrifugal pumps for transporting flows with dilute particles is a main pump failure problem in many engineering processes. A numerical model combining the computational fluid dynamics (CFD) and Discrete Element Method (DEM) is applied to simulate erosion in a centrifugal pump. Different models of the liquid-solid inter-phase forces are implemented, and the particle-turbulence interaction is also defined. The inertial particles considered in this work are monodisperse and have finite size. The numerical results are validated by comparing the results with a series of experimental data. Then, the effects of particle volume fraction, size, and shape on the pump erosion are estimated in the simulations. The results demonstrate that severe erosive areas are located near the inlet and outlet of the pressure side of the impeller blade, the middle region of the blade, the corners of the shroud and hub of the impeller adjoining to the pressure side of the blade, and the volute near the pump tongue. Among these locations, the maximum erosion occurs near the inlet of the pressure side of the blade. Erosion mitigation occurs under the situation where more particles accumulate in the near-wall region of the eroded surface, forming a buffering layer. The relationship between the particle size and the erosion is nonlinear, and the 1 mm particle causes the maximum pump erosion. The sharp particles cause more severe erosion in the pump because both the frequency of particle-wall collisions and the impact angle increase with the increasing sharpness of the particle.

Molecular identification and characterization of ‘Candidatus Phytoplasma asteris’-related strain associated with pepper (Capsicum annuum L.) yellow crinkle disease in China - Shao-shuai Yu; Qing-hua Tang; Deng-qiang Fu; Rui-ling Zhao; Wei-wei Song; Wei Yan; Wei-quan Qin (Journal of General Plant Pathology, 2021)

Catalytic Hydroprocessing of White Pine Pyrolysis Bio-Oil over Cobalt-Molybdenum Carbide in a Continuous Packed-Bed Reactor - Rui Li; Zhixin Zhao; Bo Zhang; Xiaozheng Sun; Zhen Zhang; Ying Zhang; Haitao Chen; Qiangu Yan (BioEnergy Research, 2021)

A novel Schiff base cobalt(III) complex induces a synergistic effect on cervical cancer cells by arresting early apoptosis stage - Wen-Hui Liao; Xue-Qing Song; Yan-Jie Kong; Rui-Dan Bao; Fang-Fang Li; Jie Zhou; Qi-Hua Zhao; Jing-Yuan Xu; Ni Xie; Ming-Jin Xie (BioMetals, 2021)

Change detection in SAR images based on superpixel segmentation and image regression - Rui Zhao; Guo-Hua Peng; Wei-dong Yan; Lu-Lu Pan; Li-Ya Wang (Earth Science Informatics, 2021)

Dynamic Variations in Brain Glycogen are Involved in Modulating Isoflurane Anesthesia in Mice - Ze Fan; Zhihao Zhang; Shiyi Zhao; Yuanyuan Zhu; Dong Guo; Bo Yang; Lixia Zhuo; Jiao Han; Rui Wang; Zongping Fang; Hailong Dong; Yan Li; et al. (Neuroscience Bulletin, 2020)
General anesthesia severely affects the metabolites in the brain. Glycogen, principally stored in astrocytes and providing the short-term delivery of substrates to neurons, has been implicated as an affected molecule. However, whether glycogen plays a pivotal role in modulating anesthesia–arousal remains unclear. Here, we demonstrated that isoflurane-anesthetized mice exhibited dynamic changes in the glycogen levels in various brain regions. Glycogen synthase (GS) and glycogen phosphorylase (GP), key enzymes of glycogen metabolism, showed increased activity after isoflurane exposure. Upon blocking glycogenolysis with 1,4-dideoxy-1,4-imino-D-arabinitol (DAB), a GP antagonist, we found a prolonged time of emergence from anesthesia and an enhanced δ frequency in the EEG (electroencephalogram). In addition, augmented expression of glycogenolysis genes in glycogen phosphorylase, brain (Pygb) knock-in (Pygb H11/H11 ) mice resulted in delayed induction of anesthesia, a shortened emergence time, and a lower ratio of EEG-δ. Our findings revealed a role of brain glycogen in regulating anesthesia–arousal, providing a potential target for modulating anesthesia.

Atrophy of right inferior frontal orbital gyrus and frontoparietal functional connectivity abnormality in depressed suicide attempters - Yuyin Yang; Mohammad Ridwan Chattun; Rui Yan; Ke Zhao; Yu Chen; Rongxin Zhu; Jiabo Shi; Xinyi Wang; Qing Lu; Zhijian Yao (Brain Imaging and Behavior, 2020)

Psychroflexus maritimus sp. nov., isolated from coastal sediment - Yan-Lin Zhong; Rui Zhang; Xiao-Yu Zhang; Li-Xue Yu; Meng-Fan Zhao; Zong-Jun Du (Archives of Microbiology, 2020)

Rapid and efficient removal of naproxen from water by CuFe2O4 with peroxymonosulfate - Rui Bai; Yong Xiao; Weifu Yan; Siqi Wang; Rui Ding; Fan Yang; Junpeng Li; Xiaoquan Lu; Feng Zhao (Environmental Science and Pollution Research, 2020)

Improvement of water quality in the Pearl River Estuary, China: a long-term (2008–2017) case study of temporal-spatial variation, source identification and ecological risk of heavy metals in surface water of Guangzhou - Yan-ping Zhao; Rui Wu; Jin-li Cui; Shu-chai Gan; Jia-chuan Pan; Peng-ran Guo (Environmental Science and Pollution Research, 2020)

The Complete Genome of Emcibacter congregatus ZYLT, a Marine Bacterium Encoding a CRISPR-Cas 9 Immune System - Zhe Zhao; Rui-an Zhang; Ge-yi Fu; Ran Zhang; Yan-fang Nie; Cong Sun; Min Wu (Current Microbiology, 2020)

Characteristics and dynamics of the Ganqiuchi rock avalanche triggered by a paleo-earthquake in the Northern Qinling Mountains - Ze-Hua Zhou; Yan Lyu; Sheng-rui Su; Shi-jie Liu; Hui Zhao; Peng Li; Yang Zhou (Journal of Mountain Science, 2020)

Correction to: Description of Wenzhouxiangella salilacus sp. nov., a moderate halophilic bacterium isolated from a salt lake in Xinjiang Province, China - Shuai-Bo Han; Xin-Jun Hou; Yang-Huan Yu; Zhao Ju; Ran Zhang; Rui-Jun Wang; Yang-Hui Ye; Yan-Hu Ren; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2020)

Application of metagenomic next-generation sequencing for bronchoalveolar lavage diagnostics in critically ill patients - Ying Li; Bing Sun; Xiao Tang; Ya-lan Liu; Hang-yong He; Xu-yan Li; Rui Wang; Fei Guo; Zhao-hui Tong (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Evaluation of Inoculum Sources for Aerobic Treatment of 2,3,4-Trifluoroaniline During Start-up and Shock - Zhi-Qing Zhao; Xiao-Li Shen; Tu-Cai Zheng; Ghulam Abbas; Rui Fan; Yan-Mei Li (Water, Air, & Soil Pollution, 2019)

Structural characterization and immunosuppressive activity of a new pregnane glycoside from Epigynum cochinchinensis - Yu-Ting Shao; Yan Zhao; Hong Zhang; Meng-Jun Jiang; Afsar Khan; Sheng-Bao Cai; Tian-Rui Zhao; Gui-Guang Cheng; Jian-Xin Cao (Natural Product Research, 2019)

Comparison of volatile profiles and bioactive components of sun-dried Pu-erh tea leaves from ancient tea plants on Bulang Mountain measured by GC-MS and HPLC - Wen-jie Zhang; Cong Liu; Rui-juan Yang; Ting-ting Zheng; Miao-miao Zhao; Li Ma; Liang Yan (Journal of Zhejiang University-SCIENCE B, 2019)

Description of Wenzhouxiangella salilacus sp. nov., a moderate halophilic bacterium isolated from a salt lake in Xinjiang Province, China - Shuai-Bo Han; Xin-Jun Hou; Yang-Huan Yu; Zhao Ju; Ran Zhang; Rui-Jun Wang; Yang-Hui Ye; Yan-Hu Ren; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2019)

Paleogene sedimentation changes in Lenghu Area, Qaidam Basin in response to the India–Eurasia collision - Rui Zhao; Si Chen; Hua Wang; Detian Yan; Haiyang Cao; Yin Gong; Jie He; Zhixiong Wu (International Journal of Earth Sciences, 2019)

Comprehensive analysis of the whole coding and non-coding RNA transcriptome expression profiles and construction of the circRNA–lncRNA co-regulated ceRNA network in laryngeal squamous cell carcinoma - Rui Zhao; Feng-Qing Li; Lin-Li Tian; De-Si Shang; Yan Guo; Jia-Rui Zhang; Ming Liu (Functional & Integrative Genomics, 2019)

Carbon pools and fluxes in the China Seas and adjacent oceans - Nianzhi Jiao; Yantao Liang; Yongyu Zhang; Jihua Liu; Yao Zhang; Rui Zhang; Meixun Zhao; Minhan Dai; Weidong Zhai; Kunshan Gao; Jinming Song; Dongliang Yuan; et al. (Science China Earth Sciences, 2018)

Use of cationic microbubbles targeted to P-selectin to improve ultrasound-mediated gene transfection of hVEGF165 to the ischemic myocardium - Wei-hui Shentu; Cao-xin Yan; Chun-mei Liu; Rui-xiang Qi; Yao Wang; Zhao-xu Huang; Li-ming Zhou; Xiang-dong You (Journal of Zhejiang University-SCIENCE B, 2018)

RNA Sequence Analysis of Cassava Varieties with High-Starch Content Using De Novo Assembly - Ya-Jing Guo; Xing-Lu Luo; Mao-Gui Wei; Zhao-Liang Liu; Wu-Jing Fan; Rui-Ning Zhai; Yan-Mei Zhu (Journal of Plant Growth Regulation, 2018)

Genomic changes in an attenuated genotype I Japanese encephalitis virus and comparison with virulent parental strain - Yuyong Zhou; Rui Wu; Yao Feng; Qin Zhao; Xintian Wen; Xiaobo Huang; Yiping Wen; Qigui Yan; Yong Huang; Xiaoping Ma; Xinfeng Han; Sanjie Cao (Virus Genes, 2018)

Identification of blasting vibration and coal-rock fracturing microseismic signals - Xing-Li Zhang; Rui-Sheng Jia; Xin-Ming Lu; Yan-Jun Peng; Wei-Dong Zhao (Applied Geophysics, 2018)

Mutation of I176R in the E coding region weakens Japanese encephalitis virus neurovirulence, but not its growth rate in BHK-21 cells - Yuyong Zhou; Rui Wu; Qin Zhao; Yung-Fu Chang; Xintian Wen; Yao Feng; Xiaobo Huang; Yiping Wen; Qigui Yan; Yong Huang; Xiaoping Ma; Xinfeng Han; et al. (Archives of Virology, 2018)

A new immunosuppressive pregnane glycoside from aqueous fraction of Epigynum cochinchinensis - Zong Wan; Yuan-Cheng Yao; Fei Gao; Sheng-Bao Cai; Afsar Khan; Tian-Rui Zhao; Xiao-Yan Yang; Jian Fan; Sheng-Yan Qian; Jian-Xin Cao; Gui-Guang Cheng (Natural Product Research, 2017)

Growth Differentiation Factor 15 Is a Novel Diagnostic Biomarker of Mitochondrial Diseases - Xinbo Ji; Lizhen Zhao; Kunqian Ji; Yuying Zhao; Wei Li; Rui Zhang; Ying Hou; Jianqiang Lu; Chuanzhu Yan (Molecular Neurobiology, 2017)

Polyamine-binding protein PotD2 is required for stress tolerance and virulence in Actinobacillus pleuropneumoniae - Zhuang Zhu; Qin Zhao; Yu Zhao; Fei Zhang; Xintian Wen; Xiaobo Huang; Yiping Wen; Rui Wu; Qigui Yan; Yong Huang; Xiaoping Ma; Xinfeng Han; et al. (Antonie van Leeuwenhoek, 2017)

Lysophosphatidic acid enhances human umbilical cord mesenchymal stem cell viability without differentiation via LPA receptor mediating manner - Narengerile Li; Ya-Li Yan; Sachaofu Fu; Rui-Juan Li; Peng-Fei Zhao; Xi-Yuan Xu; Jing-Ping Yang; Alatangaole Damirin (Apoptosis, 2017)

Correlation of rs9331888 polymorphism with Alzheimer’s disease among Caucasian and Chinese populations: a meta-analysis and systematic review - Bin Zhu; Rui Min Wang; Jian Ting Wang; Rui Ling Chen; Yan Fei Zheng; Lei Zhang; Zhi Gang Zhao (Metabolic Brain Disease, 2017)

Expression-based genotyping of the rice blast resistance genes in the elite maintainer line Yixiang1B - Li Wang; Xiao-Hong Hu; Gang Lin; De-Ming Zhao; Jun Shi; Zhi-Xue Zhao; Rui Zeng; Heng-Jing Li; De-Qiang Li; Jing Fan; Yan Li; Fu Huang; et al. (European Journal of Plant Pathology, 2017)

Enhanced dissipation of DEHP in soil and simultaneously reduced bioaccumulation of DEHP in vegetable using bioaugmentation with exogenous bacteria - Hai-Ming Zhao; Rui-Wen Hu; He-Biao Huang; Hong-Fei Wen; Huan Du; Yan-Wen Li; Hui Li; Quan-Ying Cai; Ce-Hui Mo; Jie-Sheng Liu; Ming-Hung Wong (Biology and Fertility of Soils, 2017)

Therapeutic value of nerve growth factor in promoting neural stem cell survival and differentiation and protecting against neuronal hearing loss - Zhao Han; Cong-Pin Wang; Ning Cong; Yu-Yan Gu; Rui Ma; Fang-Lu Chi (Molecular and Cellular Biochemistry, 2017)

Physiological characteristics and metabolomics of transgenic wheat containing the maize C4 phosphoenolpyruvate carboxylase (PEPC) gene under high temperature stress - Xueli Qi; Weigang Xu; Jianzhou Zhang; Rui Guo; Mingzhong Zhao; Lin Hu; Huiwei Wang; Haibin Dong; Yan Li (Protoplasma, 2017)

Demethyleneberberine alleviates inflammatory bowel disease in mice through regulating NF-κB signaling and T-helper cell homeostasis - Ying-Ying Chen; Rui-Yan Li; Mei-Jing Shi; Ya-Xing Zhao; Yan Yan; Xin-Xin Xu; Miao Zhang; Xiao-Tong Zhao; Yu-Bin Zhang (Inflammation Research, 2017)

Two new compounds from Trollius chinensis Bunge - Ya Jie-Shi; Lin Wei-Sang; Rui Yan; Qiang Zhao; Yang Zhang; Gui Yun-Zhao; Yun Cong-Li; Xue Chen; Chong Yu-Zhang; Hua Qiao; Guo Gang-Zhang (Journal of Natural Medicines, 2017)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Application of TiO2-organobentonite modified by cetyltrimethylammonium chloride photocatalyst and polyaluminum chloride coagulant for pretreatment of aging landfill leachate - Yi-Jie Zhang; Zhao-Hui Yang; Pei-Pei Song; Hai-Yin Xu; Rui Xu; Jing Huang; Juan Li; Yan Zhou (Environmental Science and Pollution Research, 2016)

Chryseobacterium chengduensis sp. nov. isolated from the air of captive giant panda enclosures in Chengdu, China - Cai-fang Wen; Li-xin Xi; Shan Zhao; Zhong-xiang Hao; Lu Luo; Hong Liao; Zhen-rong Chen; Rong She; Guo-quan Han; San-jie Cao; Rui Wu; Qi-gui Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2016)

Two new compounds from the roots of Ilex pubescens and their cytotoxic activity - Huan Xiong; Fang Zhao; Jiayi Bi; Yang Zhang; Guiyun Zhao; Xue Chen; Yuncong Li; Rui Yan; Qiang Zhao; Hua Qiao; Guogang Zhang (Journal of Natural Medicines, 2016)

Improvement of soybean transformation via Agrobacterium tumefaciens methods involving α-aminooxyacetic acid and sonication treatments enlightened by gene expression profile analysis - Yan-Min Zhang; Zi-Hui Liu; Rui-Juan Yang; Guo-Liang Li; Xiu-Lin Guo; Hua-Ning Zhang; Hong-Mei Zhang; Rui Di; Qing-Song Zhao; Meng-Chen Zhang (Plant Cell Reports, 2016)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

Ochrobactrum endophyticum sp. nov., isolated from roots of Glycyrrhiza uralensis - Li Li; Yan-Qiong Li; Zhao Jiang; Rui Gao; Salam Nimaichand; Yan-Qing Duan; Dilfuza Egamberdieva; Wei Chen; Wen-Jun Li (Archives of Microbiology, 2016)

Breeding of an intraspecific kelp hybrid Dongfang no. 6 (Saccharina japonica, Phaeophyceae, Laminariales) for suitable processing products and evaluation of its culture performance - Xiaojie Li; Zhuangzhi Zhang; Shancun Qu; Guangjin Liang; Nan Zhao; Juan Sun; Shaofeng Song; Zengmei Cao; Xia Li; Jinhua Pan; Shiju Luo; Linan Zhang; et al. (Journal of Applied Phycology, 2016)

Lysobacter chengduensis sp. nov. Isolated from the Air of Captive Ailuropoda melanoleuca Enclosures in Chengdu, China - Caifang Wen; Lixin Xi; Rong She; Shan Zhao; Zhongxiang Hao; Lu Luo; Hong Liao; Zhenrong Chen; Guoquan Han; Sanjie Cao; Rui Wu; Qigui Yan; et al. (Current Microbiology, 2016)

RETRACTED ARTICLE: Effects of Repetitive Transcranial Magnetic Stimulation on Cognitive Impairment in Stroke Patients: A Meta-Analysis - Lei Cao; Rui Zhao; Su Huo; Ju-Bao Du; Lin Liu; Yan-Ming Zhang; Wei-Qun Song (Molecular Neurobiology, 2015)

Retraction Note to: Uncovering the pathogenesis and identifying novel targets of pancreatic cancer using bioinformatics approach - Li-Li Zhao; Tong Zhang; Li-Wei Zhuang; Bing-Zhu Yan; Rui-Feng Wang; Bing-Rong Liu (Molecular Biology Reports, 2015)

Changes in global DNA methylation intensity and DNMT1 transcription during the aging process of scallop Chlamys farreri - Shanshan Lian; Yan He; Xue Li; Bosong Zhao; Rui Hou; Xiaoli Hu; Lingling Zhang; Zhenmin Bao (Journal of Ocean University of China, 2015)

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

Needle-free injection of insulin powder: delivery efficiency and skin irritation assessment - Chun-yu Li; Zhe-wei Wang; Can Tu; Jia-bo Wang; Bing-qian Jiang; Qi Li; Ling-na Zeng; Zhi-jie Ma; Ping Zhang; Yan-ling Zhao; Ya-ming Zhang; Dan Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Toxic effects of sodium fluoride on cell proliferation and apoptosis of Leydig cells from young mice - Guo hua Song; Rui Li Wang; Zhao Yang Chen; Bin Zhang; Hai Long Wang; Mao Lin Liu; Ji Ping Gao; Xiao Yan Yan (Journal of Physiology and Biochemistry, 2014)

Isolation and characterization of nineteen novel polymorphic microsatellite loci for the northern snakehead Channa argus - Ruo-Jin Yan; Kai-Jian Wei; Xiang-Zhao Guo; Gui-Rong Zhang; Jonathan P. A. Gardner; Rui-Bin Yang; Kun-Ci Chen (Conservation Genetics Resources, 2014)

RETRACTED ARTICLE: Uncovering the pathogenesis and identifying novel targets of pancreatic cancer using bioinformatics approach - Li-Li Zhao; Tong Zhang; Li-Wei Zhuang; Bing-Zhu Yan; Rui-Feng Wang; Bing-Rong Liu (Molecular Biology Reports, 2014)

The effect of NF-κB antisense oligonucleotide on transdifferentiation of fibroblast in lung tissue of mice injured by bleomycin - Yan Zhou; Xiaoye Zhang; Mingqi Tan; Rui Zheng; Li Zhao (Molecular Biology Reports, 2014)

Isolation and characterization of twenty-three polymorphic microsatellite loci in Schizothorax macropogon - Xiang-Zhao Guo; Gui-Rong Zhang; Ruo-Jin Yan; Wei Ji; Rui-Bin Yang; Kai-Jian Wei; Deng-Qiang Wang (Conservation Genetics Resources, 2014)

The Neuroprotective Effects of Isoflurane Preconditioning in a Murine Transient Global Cerebral Ischemia–Reperfusion Model: The Role of the Notch Signaling Pathway - Hao-peng Zhang; Yan-yan Sun; Xiao-mei Chen; Li-bang Yuan; Bin-xiao Su; Rui Ma; Rui-ni Zhao; Hai-long Dong; Lize Xiong (NeuroMolecular Medicine, 2014)

Effects of submerged macrophytes on the abundance and community composition of ammonia-oxidizing prokaryotes in a eutrophic lake - Da-yong Zhao; Juan Luo; Jin Zeng; Meng Wang; Wen-ming Yan; Rui Huang; Qinglong L. Wu (Environmental Science and Pollution Research, 2014)

Effect of sulphate nutrition on arsenic translocation and photosynthesis of rice seedlings - Rui Song; Chen-Yun Zhao; Juan Liu; Jing Zhang; Yan-Xiu Du; Jun-Zhou Li; Hong-Zheng Sun; Hong-Bing Zhao; Quan-Zhi Zhao (Acta Physiologiae Plantarum, 2013)

Association between interferon gamma +874 T>A polymorphism and acute renal allograft rejection: evidence from published studies - Yu-Zheng Ge; Ran Wu; Rui-Peng Jia; Hao Liu; Peng Yu; Yan Zhao; Yu-Ming Feng (Molecular Biology Reports, 2013)

In vitro mutagenesis and directed screening for salt-tolerant mutants in peanut - Ming-Xia Zhao; Hai-Yan Sun; Rui-Rui Ji; Xiao-Hui Hu; Jiong-Ming Sui; Li-Xian Qiao; Jing Chen; Jing-Shan Wang (Euphytica, 2013)

Litorilituus sediminis gen. nov. sp. nov., isolated from coastal sediment of an amphioxus breeding zone in Qingdao, China - Yan Wang; Rui Zhao; Shiqi Ji; Zhao Li; Tong Yu; Bingyu Li; Xiaochong Shi; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2013)

Genome-wide identification and transcription analysis of soybean carotenoid oxygenase genes during abiotic stress treatments - Rui-Kai Wang; Chun-E Wang; Yun-Yan Fei; Jun-Yi Gai; Tuan-Jie Zhao (Molecular Biology Reports, 2013)

Determination of oxidized scytonemin in Nostoc commune Vauch cultured on different conditions by high performance liquid chromatography coupled with triple quadrupole mass spectrometry - Juanjuan Chen; Lijuan Zhao; Jilin Xu; Rui Yang; Shan He; Xiaojun Yan (Journal of Applied Phycology, 2013)

Meso-Cenozoic extensional structures in the Northern Tarim Basin, NW China - Yue-Jun Li; Yan Zhao; Long-De Sun; Wen-Jie Song; Duo-Ming Zheng; Ya-Lei Liu; Dao-Xuan Wang; Jian-Feng Hu; Qi-Rui Zhang (International Journal of Earth Sciences, 2013)

Molecular cloning and functional analysis of a blue light receptor gene MdCRY2 from apple (Malus domestica) - Yuan-Yuan Li; Ke Mao; Cheng Zhao; Xian-Yan Zhao; Rui-Fen Zhang; Hua-Lei Zhang; Huai-Rui Shu; Yu-Jin Hao (Plant Cell Reports, 2013)

Inhibition of autophagy enhances anticancer effects of bevacizumab in hepatocarcinoma - Xian-ling Guo; Ding Li; Kai Sun; Jin Wang; Yan Liu; Jian-rui Song; Qiu-dong Zhao; Shan-shan Zhang; Wei-jie Deng; Xue Zhao; Meng-chao Wu; Li-xin Wei (Journal of Molecular Medicine, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Litoribacillus peritrichatus gen. nov. sp. nov., isolated from coastal sediment of an amphioxus breeding zone in Qingdao, China - Rui Zhao; Shiqi Ji; Yan Wang; Tong Yu; Zhao Li; Bingyu Li; Xiaochong Shi; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2013)

Diversity analysis of bacterial community compositions in sediments of urban lakes by terminal restriction fragment length polymorphism (T-RFLP) - Dayong Zhao; Rui Huang; Jin Zeng; Wenming Yan; Jianqun Wang; Ting Ma; Meng Wang; Qinglong L. Wu (World Journal of Microbiology and Biotechnology, 2012)

Construction of self-cloning, indigenous wine strains of Saccharomyces cerevisiae with enhanced glycerol and glutathione production - Rui-Ying Hao; Yan-Lin Liu; Zhao-Yue Wang; Bo-run Zhang (Biotechnology Letters, 2012)

Gastrin inhibits a novel, pathological colon cancer signaling pathway involving EGR1, AE2, and P-ERK - Ling-Jun Song; Rui-Jun Liu; Zhi Zeng; Seth L. Alper; Heng-Jing Cui; Yang Lu; Lin Zheng; Zhao-Wen Yan; Guo-Hui Fu (Journal of Molecular Medicine, 2012)

Chemical composition and antioxidant activities of extracts from Apocyni Veneti Folium - Sui-Hong Yan; Ying-Yong Zhao; Hai-Song Zeng; Yongmin Zhang; Rui-Chao Lin; Wen-Ji Sun (Natural Product Research, 2012)

Nicotinic acetylcholine receptor alpha7 subunit is time-dependently expressed in distinct cell types during skin wound healing in mice - Yan-Yan Fan; Tian-Shui Yu; Tao Wang; Wei-Wei Liu; Rui Zhao; Shu-Tao Zhang; Wen-Xiang Ma; Ji-Long Zheng; Da-Wei Guan (Histochemistry and Cell Biology, 2011)

Isolation and characterization of a gene encoding a polyethylene glycol-induced cysteine protease in common wheat - Qing-Wei Zang; Cai-Xiang Wang; Xu-Yan Li; Zhi-Ai Guo; Rui-Lian Jing; Jun Zhao; Xiao-Ping Chang (Journal of Biosciences, 2010)

The influence of ADAR1’s regulation on lymphocyte cell function during rejection - Lei Cai; Yan Li; Feng Liu; Wei Zhang; Binliang Huo; Wei Zheng; Rui Ding; Jiyuan Guo; Qingchuan Zhao; Kefeng Dou (Molecular Biology Reports, 2010)

14-3-3γ and Neuroglobin are New Intrinsic Protective Factors for Cerebral Ischemia - Yan Dong; Rui Zhao; Xiao Qian Chen; Albert Cheung Hoi Yu (Molecular Neurobiology, 2010)

Fluorescent Property of the Gd3+-Doped Terbium Complexes and Crystal Structure of [Tb(TPTZ)(H2O)6]Cl3·3H2O - Yan-Fang Zhao; Yong-Liang Zhao; Feng Bai; Xiao-yan Wei; Yong-sheng Zhou; Mei-na Shan; Huan-huan Li; Rui-jun Ma; Xiao-tao Fu; Yan Du (Journal of Fluorescence, 2010)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

A new eremophilenolactone from Senecio nemorensis - Fan Jun Meng; Yan Nan Xiao; Rui Jian Zhao; Hong Zhao; Qing Lin Ma; Wei Dong Xie (Natural Product Research, 2009)

QTL analysis of kernel shape and weight using recombinant inbred lines in wheat - Xian-Yin Sun; Ke Wu; Yan Zhao; Fan-Mei Kong; Guan-Zhu Han; Hong-Ming Jiang; Xing-Jiao Huang; Rui-Jun Li; Hong-Gang Wang; Si-Shen Li (Euphytica, 2009)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Effects of RNA interference-induced tryptase down-regulation in P815 cells on IL-6 and TNF-α release of endothelial cells - Yi-feng Jiang; Feng-di Zhao; Xiao-bo Li; Yan-xia Ning; Xiu-ling Zhi; Rui-zhe Qian; Lian-hua Yin (Journal of Zhejiang University-SCIENCE B, 2008)

Adenovirus-mediated PDCD5 gene transfer sensitizes K562 cells to apoptosis induced by idarubicin in vitro and in vivo - Guo-Rui Ruan; Hong-Shan Zhao; Yan Chang; Jin-Lan Li; Ya-Zhen Qin; Yan-Rong Liu; Shan-Shan Chen; Xiao-Jun Huang (Apoptosis, 2008)

Isolation and molecular characterization of the Triticum aestivum L. ethylene-responsive factor 1 (TaERF1) that increases multiple stress tolerance - Zhao-Shi Xu; Lan-Qin Xia; Ming Chen; Xian-Guo Cheng; Rui-Yue Zhang; Lian-Cheng Li; Yun-Xiang Zhao; Yan Lu; Zhi-Yong Ni; Li Liu; Zhi-Gang Qiu; You-Zhi Ma (Plant Molecular Biology, 2007)

Expression of a grape calcium-dependent protein kinase ACPK1 in Arabidopsis thaliana promotes plant growth and confers abscisic acid-hypersensitivity in germination, postgermination growth, and stomatal movement - Xiang-Chun Yu; Sai-Yong Zhu; Gui-Feng Gao; Xiao-Jing Wang; Rui Zhao; Ke-Qin Zou; Xiao-Fang Wang; Xiao-Yan Zhang; Fu-Qing Wu; Chang-Cao Peng; Da-Peng Zhang (Plant Molecular Biology, 2007)

Role of iNOS-derived reactive nitrogen species and resultant nitrative stress in leukocytes-induced cardiomyocyte apoptosis after myocardial ischemia/reperfusion - Xiao-Liang Wang; Hui-Rong Liu; Lin Tao; Feng Liang; Li Yan; Rong-Rui Zhao; Bernard L. Lopez; Theodore A. Christopher; Xin-Liang Ma (Apoptosis, 2007)

Transgenic Mice Can Express Mutant Human Coagulation Factor IX with Higher Level of Clotting Activity - Jing-Bin Yan; Shu Wang; Wen-Ying Huang; Yan-Ping Xiao; Zhao-Rui Ren; Shu-Zheng Huang; Yi-Tao Zeng (Biochemical Genetics, 2006)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)